Adhesive tape

The adhesive tape with a triblock copolymer and resin-modified resin structure addresses the challenges of maintaining high load holding force and ease of peeling, ensuring effective reuse and stability across different environments.

JP7622761B2Active Publication Date: 2025-01-28DIC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023020711
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-21
Filing Date
2023-02-14
Publication Date
2025-01-28
Estimated Expiration
2041-01-14

AI Technical Summary

Technical Problem

Existing adhesive tapes face challenges in maintaining high load holding force, ease of peeling, and storage stability, especially in environments with varying conditions such as high temperature and humidity, making them difficult to reuse without residue and requiring significant effort to remove.

Method used

The adhesive tape is designed with a base layer and adhesive layer containing a triblock copolymer with specific chemical structure, a resin-modified resin, and a substrate layer with controlled tensile strength and extension, ensuring high load holding force and ease of peeling, even after prolonged use or in challenging environments.

Benefits of technology

The adhesive tape provides excellent high load holding force, ease of peeling, and preserved stability, allowing for easy removal without residue, even after prolonged use or in varying environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622761000001
    Figure 0007622761000001
  • Figure 0007622761000002
    Figure 0007622761000002
  • Figure 0007622761000003
    Figure 0007622761000003
Patent Text Reader

Abstract

Provided is an adhesive tape having high load-holding power, excellent removability over time, and excellent adhesive strength with excellent storage stability. The adhesive tape includes a base layer and an adhesive layer, wherein the base layer has a breaking stress of 1 to 100 MPa and a breaking elongation of 400 to 3000%, and the adhesive layer contains a tackifier resin and a compound represented by the general formula (1): TIFF2023058655000015.tif13150 (In the above general formula (1), A, B, and C each independently represent a repeating unit, A and C each independently represent a methacrylic acid alkyl ester monomer unit, B represents an acrylic acid alkyl ester monomer unit, p, q, and r each independently represent the degree of polymerization of each monomer unit, and A and C may be methacrylic acid alkyl ester monomer units having the same or different chemical structures. In the above general formula (1), * represents a bond to another atom.)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive tape. [Background technology]

[0002] The adhesive tape has excellent workability and high adhesive reliability. Therefore, the adhesive tape is widely used as a joining means in the fixing of parts constituting relatively large electronic devices such as flat-screen televisions, home appliances, and office automation equipment, or relatively small electronic devices such as mobile electronic terminals, cameras, and personal computers. More specifically, in various industrial fields such as office automation equipment, IT, home appliances, and automobiles, the adhesive tape is used not only for fixing parts such as fixing sheet metals constituting large electronic devices, fixing exterior parts and housings, and fixing rigid parts such as exterior parts or batteries to small electronic devices, and for temporary fixing of the parts, but also for labeling purposes that display product information.

[0003] In recent years, in order to conserve resources from the viewpoint of protecting the global environment, there has been an increasing tendency in the above-mentioned industrial fields to disassemble used products and reuse or recycle the reusable or reusable parts used in the products. In this case, if an adhesive tape is used, it is necessary to peel off the adhesive tape attached to the parts. However, since the adhesive tape usually has a high adhesive strength and is attached to many parts in the product, the work of peeling it off involves a considerable amount of labor. Therefore, there is a demand for an adhesive tape that can be relatively easily peeled off and removed when reused or re-used.

[0004] As an example of a technology relating to an adhesive tape that can be easily peeled and removed, Patent Document 1 can be mentioned. Patent Document 1 discloses an adhesive tape that has an adhesive part and a tab part, and can be peeled off from an adherend attached to both sides of the adhesive part by pinching the tab part and stretching it in a direction approximately parallel to the adhesive surface. However, in a small electronic device, since the space between the components in the electronic device is narrow, there is a problem that it is difficult to stretch and peel off the adhesive tape attached to the space in a direction parallel to the adhesive surface. As a technology to solve this problem, Patent Document 2 discloses an adhesive tape that can be removed again by stretching it in a 30° direction relative to the adhesive surface. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-124289 A [Patent Document 2] JP 2016-26255 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the above Patent Document 1, the adhesive tape is cured in an oven at 40°C for 30 minutes, and then the adhesive tape is evaluated for its holding power when a weight of 1 kg is hung from it. In addition, in the above Patent Document 2, the adhesive article is examined for its ability to be stretched and removed without breaking or leaving any adhesive residue. However, the techniques of the above Patent Documents 1 and 2 do not examine the high load holding power that maintains the adhesive power under a higher load. In addition, after a certain period of time has passed since the adhesive tape or adhesive article is applied to the adherend, the adhesion to the adherend is further increased, which causes a problem that removability from the adherend becomes difficult. However, the techniques of the above Patent Documents 1 and 2 do not examine such removability over time at all. Furthermore, the adhesive tape, such as the manufactured adhesive tape or adhesive article, is stored under various environments until it is used. In this case, depending on the storage environment (for example, under high temperature and humidity), there is a problem that the adhesive strength of the adhesive tape decreases before it is used, and it is also necessary to have storage stability of the adhesive strength that can maintain the initial performance until the adhesive tape is used.

[0007] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a pressure-sensitive adhesive tape having excellent adhesive strength with respect to high load-holding power, removability over time, and storage stability. [Means for solving the problem]

[0008] In view of the above problems, the inventors conducted intensive research and discovered that the above problems could be solved by using an adhesive layer containing a triblock copolymer having a specific chemical structure and a base layer having specific tensile strength and elongation, thereby completing the present invention.

[0009] That is, the present invention is as follows. [1] The present invention provides an adhesive tape having a base layer and an adhesive layer, The base layer has a breaking stress of 1 to 100 MPa and a breaking elongation of 300 to 3000%, The adhesive layer comprises a tackifier resin and a compound represented by the general formula (1): [ka] (In the above general formula (1), A, B, and C each independently represent a repeating unit, A and C each independently represent a methacrylic acid alkyl ester monomer unit, B represents an acrylic acid alkyl ester monomer unit, p, q, and r each independently represent the degree of polymerization of each monomer unit, and A and C may be methacrylic acid alkyl ester monomer units having the same or different chemical structures. In the above general formula (1), * represents a bond to another atom.)

[0010] [2] In the present invention, the triblock copolymer preferably has a weight average molecular weight Mw of 50,000 to 300,000 and a number average molecular weight Mn of 50,000 to 300,000.

[0011] [3] In the present invention, the softening point of the tackifier resin is preferably 95° C. or higher.

[0012] [4] In the present invention, it is preferable that the softening point temperature [°C] of the tackifier resin × the amount of the tackifier resin added (the amount of the tackifier resin added when the triblock copolymer is 100 parts by mass) is 1,300 to 13,000.

[0013] [5] In the present invention, the base layer preferably contains a vinyl aromatic block copolymer.

[0014] [6] In the present invention, it is preferable that the peel adhesion strength is 5 N / 20 mm or more.

[0015] [7] In the present invention, the shear adhesive strength is preferably 1.0 MPa or more.

[0016] [8] In the present invention, the adhesive layer preferably contains 10 to 150 parts by mass of the tackifier resin per 100 parts by mass of the triblock copolymer.

[0017] [9] In the present invention, the adhesive layer preferably contains a filler. Effect of the Invention

[0018] The present invention can provide a pressure-sensitive adhesive tape having excellent adhesive strength with high load-holding power, removability over time, and storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail, but the present invention is not limited to the present embodiment.

[0020] The adhesive tape of the present embodiment is an adhesive tape including a base layer and an adhesive layer. The base layer has a breaking stress of 1 to 100 MPa. The base layer has a breaking elongation of 300 to 3000%. The adhesive layer further comprises a tackifier resin and a compound represented by the general formula (1): [ka] (In the above general formula (1), A, B, and C each independently represent a repeating unit, A and C each independently represent a methacrylic acid alkyl ester monomer unit, B represents an acrylic acid alkyl ester monomer unit, p, q, and r each independently represent the degree of polymerization of each monomer unit, and A and C may be methacrylic acid alkyl ester monomer units having the same or different chemical structures. In the above general formula (1), * represents a bond to another atom.)

[0021] The pressure-sensitive adhesive tape of the present embodiment has such a configuration, and thus can ensure adhesive strength with excellent load-holding power, removability over time, and storage stability.

[0022] Specifically, the base layer of the adhesive tape of this embodiment has a breaking stress of 1 to 100 MPa and a breaking elongation of 300 to 3000%, so that in the initial stage of peeling the adhesive tape from the adherend (initial elongation of the adhesive tape), the operator can pull with a relatively light force, and through the peeling operation, the operator can peel the adhesive tape from the adherend without tearing even when pulling at a relatively fast speed (removable).

[0023] Furthermore, since the adhesive layer of the adhesive tape of this embodiment essentially contains a tackifier resin and the triblock copolymer represented by the above general formula (1), it is possible to ensure adhesive strength with excellent load retention, removability over time, and storage stability due to its extremely high elastic modulus.

[0024] The adhesive tape according to the present invention has an adhesive layer on at least one side of the base layer in contact with the base layer. The adhesive tape according to the present invention may also have two adhesive layers on both sides of the base layer in contact with the base layer, if necessary, and in this case, the two adhesive layers may be the same or different. The adhesive tape according to the present invention is not only a general term for a tape having an adhesive layer on one or both sides of a base layer and wound into a roll, but also includes a plate-shaped tape having an adhesive layer on one or both sides of a base layer and having a release liner attached thereto.

[0025] The base layer and the adhesive layer constituting the adhesive tape according to the present invention will be described in detail below. In this embodiment, the adhesive tape includes at least one adhesive layer and a base layer in contact with the adhesive layer, the base layer having a breaking stress of 1 to 100 MPa and a breaking elongation of 400 to 3000%.

[0026] In this embodiment, the base material layer is not particularly limited as long as it has the above-mentioned characteristics, and can be appropriately selected from among known materials that can be used in pressure-sensitive adhesive tapes. It is preferable that the base material layer contains the following base material materials, and may further contain other components as necessary.

[0027] The base layer may have a single layer structure, or a multi-layer structure of two layers, three layers, or more. In the present embodiment, the base layer has a breaking stress of 1 to 100 MPa, preferably 10 to 90 MPa, more preferably 15 to 90 MPa, even more preferably 30 to 90 MPa, and even more preferably 50 to 90 MPa. When the breaking stress is 1 MPa or more, the adhesive tape can be peeled off from the adherend without being torn even if the worker pulls the adhesive tape when peeling it off from the adherend. When the breaking stress is 100 MPa or less, the worker can avoid excessive stress when pulling the adhesive tape.

[0028] The breaking stress of the base material layer refers to the stress value measured when the base material layer was punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, until it broke.

[0029] The breaking stress can be adjusted by appropriately selecting the material and by applying stretching during the manufacturing process of the base layer.

[0030] In this embodiment, the base layer has a breaking elongation of 300 to 3000%, preferably 500 to 2500%, more preferably 530 to 1700%, even more preferably 560 to 1300%, and even more preferably 600 to 1200%. By having a breaking elongation of 400% or more, even if the adhesive tape is firmly attached to the adherend, the stress when peeling off the adhesive tape is not too large. In addition, by having a breaking elongation of 3000% or less, the stretching distance when peeling off the adhesive tape is not too long, making it possible to work in a small space.

[0031] The breaking elongation of the base material layer refers to the tensile elongation percentage measured when the base material layer was punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the length direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, and breaking.

[0032] The breaking elongation can be adjusted by appropriately selecting the material and by applying stretching during the manufacturing process of the base layer.

[0033] In this embodiment, the base layer preferably has a 50% modulus of 0.1 to 5 MPa, more preferably 0.5 to 4.5 MPa, and even more preferably 1 to 4 MPa. When the 50% modulus is 0.1 MPa or more, defects associated with deformation such as slippage when a load is applied to the adhesive tape or adherend can be suppressed. Furthermore, when the 50% modulus is 5 MPa or less, an operator can pull the adhesive tape from the adherend with a relatively light force in the initial stage of peeling it off.

[0034] The 50% modulus of the base layer refers to the stress value measured when the base layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, and the elongation is 50%.

[0035] The 50% modulus can be adjusted by appropriately selecting the material and by applying stretching during the manufacturing process of the base layer.

[0036] In this embodiment, the base layer preferably has a rubber hardness of 25 to 90 A, more preferably 30 to 85 A, and further preferably 35 to 80 A. A rubber hardness of 25 A or more can prevent the adhesive tape from tearing when stretching and peeling it off. In addition, a rubber hardness of 90 A or less makes the base layer soft, and for example, when an adherend to which the adhesive tape is attached is dropped, the adhesive tape is more likely to absorb the impact, and the adherend can be protected from the impact (the impact resistance of the adhesive tape can be improved).

[0037] The rubber hardness of the base layer is Shore A hardness, and refers to a value measured in accordance with JIS K 6253 using a durometer (spring type rubber hardness meter) (model: GS-719G, manufactured by Teclock Corporation).

[0038] In addition, the rubber hardness can be adjusted by appropriately selecting the material, for example, by changing the molecular weight of the resin, or by changing the monomer unit if a styrene monomer unit is contained.

[0039] The base layer has an average thickness of 10 to 500 μm, preferably 30 to 250 μm, and more preferably 50 to 200 μm. A thickness of 10 μm or more ensures the strength of the adhesive tape, while a thickness of 500 μm or less prevents the adhesive tape from becoming too thick and difficult to pull.

[0040] In this specification, the "thickness of the base layer" refers to the average value of the thicknesses measured at any five points in the base layer using a TH-104 paper / film thickness meter (manufactured by Tester Sangyo Co., Ltd.).

[0041] The thickness ratio of the adhesive layer to the base layer is not particularly limited and can be appropriately selected according to the purpose, but the ratio of the thickness of the adhesive layer to the thickness of the base layer, expressed as [thickness of the adhesive layer / thickness of the base layer], is preferably 1 / 6 to 6 / 1, more preferably 1 / 3 to 3 / 1, and even more preferably 1 / 2 to 2 / 1. When the thickness ratio of the adhesive layer to the thickness of the base layer is within a preferred range, the adhesive tape can have excellent adhesion and removability (ease of peeling). On the other hand, when the ratio is greater than 6 / 1, there is a possibility that only the adhesive layer will remain on the adherend in the removability process of the adhesive tape. In addition, when the ratio is less than 1 / 6, there is a concern that the adhesive layer will not be able to follow the surface of the adherend when it has an uneven shape, etc., and the adhesive strength will decrease.

[0042] The material of the base layer is not particularly limited as long as it can provide a base layer having the above-mentioned specific physical properties, but it is preferable to have a vinyl aromatic block copolymer. When the material of the base layer is mainly composed of a vinyl aromatic block copolymer (a component contained in the total material of the base layer in an amount of more than 50 mass%), the compatibility with the triblock copolymer contained in the adhesive layer is improved, and the adhesive strength between the adhesive layer and the base layer is further improved. Specifically, the vinyl aromatic block copolymer is preferably contained in an amount of 5 to 50 mass%, more preferably 5 to 40 mass%, and more preferably 10 to 30 mass% relative to the total amount of the base layer.

[0043] Examples of materials for the substrate layer include styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, styrene-isoprene-butadiene-styrene copolymers, styrene-butadiene-styrene copolymers, styrene-ethylene-butylene copolymers, and styrene-ethylene-propylene copolymers; polyurethane resins such as ester-based polyurethanes and ether-based polyurethanes; polyolefin resins such as polyethylene and polypropylene; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polystyrene; polycarbonate; polymethylpentene; polysulfone; polyether ether ketone; polyether sulfone; polyether imide; polyimide film; fluorine resins; nylon; and acrylic resins. These may be used alone or in combination of two or more, but it is preferable to use two or more.

[0044] Among these, styrene-based resins or polyurethane resins are preferred because suitable breaking stress and breaking elongation can be easily obtained, styrene-based resins are more preferred, and it is particularly preferred to use a combination of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer.

[0045] Examples of the vinyl aromatic block copolymer include styrene-isoprene block copolymer, styrene-isoprene-styrene block copolymer, styrene-isoprene-butadiene-styrene block copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene block copolymer, styrene-ethylene-propylene block copolymer, and hydrogenated types thereof, and the like. In particular, the hydrogenated type of styrene-isoprene-butadiene-styrene block copolymer is preferred.

[0046] The styrene-based resin is a resin exhibiting thermoplasticity, and therefore has excellent moldability in extrusion molding, injection molding, etc., and is easy to mold into a substrate layer. Moreover, the styrene-based resin is particularly likely to have excellent breaking elongation among the group of resins generally called thermoplastic resins, and can be suitably used as a substrate for a pressure-sensitive adhesive sheet.

[0047] Therefore, in the material of the base layer, the proportion (mass%) of the styrene resin relative to the total resin components is preferably 50 to 100 mass%, more preferably 60 to 100 mass%, further preferably 65 to 100 mass%, and particularly preferably 70 to 100 mass%. By having the proportion of the styrene resin within the above-mentioned preferred range, a base layer excellent in breaking elongation and breaking stress can be obtained.

[0048] The styrene resin may be, for example, a single structure such as a linear structure, a branched structure, or a multi-branched structure, or may be a mixture of different structures. A styrene resin rich in linear structures can provide excellent elongation at break to the base layer. On the other hand, a branched or multi-branched structure having a styrene block at the molecular end can have a pseudo-crosslinked structure and can provide excellent cohesive strength. For this reason, it is preferable to use a mixture of styrene resins according to the required mechanical properties.

[0049] As the styrene-based resin, it is preferable to use one having a structural unit represented by the following chemical formula (A) in the range of 5 to 50 mass % relative to the total mass of the styrene-based resin, more preferably one having the structural unit represented by the following chemical formula (A) in the range of 5 to 40 mass %, even more preferably one having the structural unit represented by the following chemical formula (A) in the range of 10 to 30 mass %, and particularly preferably one having the structural unit represented by the following chemical formula (A) in the range of 15 to 25 mass %. When the ratio of the structural unit represented by the following chemical formula (A) to the total mass of the styrene-based resin is within the above-mentioned preferred range, it becomes easier to obtain a breaking elongation and breaking stress in a suitable range. In addition, * in the following chemical formula (A) is a bond representing a bond with another atom, and the same applies to the chemical formulas (B) and (1) to (3) described later. [ka] When a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer are used in combination as the styrene-based resin, the content of the styrene-isoprene copolymer relative to the total mass of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer is preferably 0 to 80 mass%, more preferably 0 to 70 mass%, further preferably 0 to 50 mass%, and particularly preferably 0 to 30 mass%. When the content of the styrene-isoprene copolymer is within the above-mentioned preferred range, it is possible to achieve both excellent thermal durability while maintaining excellent breaking elongation and breaking stress.

[0050] The styrene-isoprene copolymer preferably has a weight average molecular weight measured in terms of standard polystyrene using gel permeation chromatography (GPC) in the range of 10,000 to 800,000, more preferably in the range of 30,000 to 500,000, and even more preferably in the range of 50,000 to 300,000. The weight average molecular weight of the styrene-isoprene copolymer within the above preferred range can ensure heat flowability and compatibility when diluted with a solvent, and therefore is preferable because it is possible to obtain a base layer having good workability in the production process and heat durability.

[0051] Here, the weight average molecular weight of the styrene-isoprene copolymer is measured by the GPC method using a GPC apparatus (SC-8020, manufactured by Tosoh Corporation) and is a value converted into standard polystyrene. The measurement conditions are as follows. -Measurement conditions- Sample concentration: 0.5% by mass (tetrahydrofuran solution) Sample injection volume: 100μL Eluent: Tetrahydrofuran · Flow rate: 1.0mL / min · Measurement temperature: 40℃ - Column: TSKgel® GMHHR-H(20) x 2 Guard column: TSKgel HXL-H Detector: Differential refractometer Standard polystyrene molecular weight: 10,000 to 20 million (Tosoh Corporation) The method for producing the styrene-isoprene copolymer, the styrene-isoprene-styrene copolymer, and the mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. The block copolymer can be obtained by an anionic living polymerization method, and a coupling agent can be added and reacted as necessary.

[0052] Specifically, the method for producing a styrene-isoprene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods, such as a method in which a styrene block and an isoprene block are sequentially polymerized by an anionic living polymerization method.

[0053] The method for producing a styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. Examples of the method include a method in which a styrene block and an isoprene block are sequentially polymerized by an anionic living polymerization method, and a method in which a block copolymer having a living active end is produced and then reacted with a coupling agent to produce a coupled block copolymer.

[0054] The method for producing the mixture of styrene-isoprene copolymer and styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. For example, a method of mixing the styrene-isoprene copolymer produced by the above method with a styrene-isoprene-styrene copolymer can be mentioned. As a method for producing a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer, it is also possible to produce them as a mixture simultaneously in one polymerization step.

[0055] In a more specific embodiment, the anionic living polymerization method is as follows: first, a styrene monomer is polymerized in a polymerization solvent using an anionic polymerization initiator to form a polystyrene block having a living active end; second, isoprene is polymerized from the living active end of the polystyrene block to obtain a styrene-isoprene diblock copolymer having a living active end; third, a part of the styrene-isoprene diblock copolymer having a living active end is reacted with a coupling agent to form a coupled styrene-isoprene-styrene block copolymer; fourth, the remaining part of the styrene-isoprene diblock copolymer having a living active end is deactivated at its living active end using a polymerization terminator to form a styrene-isoprene diblock copolymer; and the styrene-isoprene diblock copolymer may be used as the vinyl aromatic block copolymer.

[0056] The polyurethane resin is not particularly limited and may be appropriately selected depending on the purpose, but preferably has a softening point of 45° C. or higher, and more preferably has a softening point of 55° C. or higher. The upper limit of the softening point is preferably 110° C. or lower. In this specification, the "softening point" refers to a value measured in accordance with JIS K 2207 (ring and ball method) (hereinafter, the softening point is measured by the same method).

[0057] As the polyurethane resin, a reaction product of a polyol (b1-1) and a polyisocyanate (b1-2) can be suitably used.

[0058] The polyol (b1-1) is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include polyester polyol, polyether polyol, polycarbonate polyol, and acrylic polyol. These may be used alone or in combination of two or more. Among these, polyester polyol and polyether polyol are preferred as the polyol (b1-1) because they can provide the mechanical properties of the base layer. When heat resistance is required in the base layer, it is preferred to use polyester polyol, and when water resistance or biodegradability is required, it is preferred to use polyether polyol.

[0059] Examples of the polyester polyol include polyesters obtained by an esterification reaction between a low molecular weight polyol and a polycarboxylic acid, polyesters obtained by a ring-opening polymerization reaction of a cyclic ester compound such as ε-caprolactone, and copolymer polyesters thereof.

[0060] Examples of low molecular weight polyols that can be used in producing the polyester polyols include aliphatic alkylene glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, and 1,3-butanediol, each of which has a weight average molecular weight of about 60 to 280, and cyclohexanedimethanol.

[0061] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; and anhydrides or esters thereof.

[0062] The polyether polyol may, for example, be one obtained by addition polymerization of an alkylene oxide using one or more compounds having two or more active hydrogen atoms as an initiator.

[0063] As the polycarbonate polyol, for example, one obtained by reacting a carbonate ester and / or phosgene with a low molecular weight polyol described below can be used.

[0064] Examples of the carbonate ester include methyl carbonate, dimethyl carbonate, ethyl carbonate, diethyl carbonate, cyclocarbonate, and diphenyl carbonate.

[0065] Examples of low molecular weight polyols that can be used in the production of the polycarbonate polyols and that can react with carbonate esters and / or phosgene include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, tripropylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 2,5-hexanediol, Examples of such phenols include 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,4-cyclohexanedimethanol, hydroquinone, resorcinol, bisphenol A, bisphenol F, and 4,4'-biphenol.

[0066] The polyisocyanate (b1-2) is not particularly limited and can be appropriately selected depending on the purpose, and examples of the polyisocyanate that can be used include alicyclic polyisocyanates, aliphatic polyisocyanates, aromatic polyisocyanates, etc., and examples of the polyisocyanate include alicyclic polyisocyanates, etc. These may be used alone or in combination of two or more kinds.

[0067] Examples of the alicyclic polyisocyanate include isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, 2,4-methylcyclohexane diisocyanate, 2,6-methylcyclohexane diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, 2,6-norbornane diisocyanate, dimer acid diisocyanate, bicycloheptane triisocyanate, etc. These may be used alone or in combination of two or more.

[0068] The method for producing the polyurethane resin (b1) by reacting the polyol (b1-1) with the polyisocyanate (b1-2) is not particularly limited and may be appropriately selected from conventionally known production methods. For example, there may be mentioned a method in which the polyol (b1-1) charged in a reaction vessel is heated under normal pressure or reduced pressure conditions to remove moisture, and then the polyisocyanate (b1-2) is supplied all at once or in portions and reacted.

[0069] The reaction between the polyol (b1-1) and the polyisocyanate (b1-2) is preferably carried out in such a manner that the equivalent ratio (NCO / OH equivalent ratio) of the isocyanate group (NCO) in the polyisocyanate (b1-2) to the hydroxyl group (OH) in the polyol (b1-1) is in the range of 1.0 to 20.0, more preferably in the range of 1.1 to 13.0, even more preferably in the range of 1.2 to 5.0, and particularly preferably in the range of 1.5 to 3.0.

[0070] The reaction conditions for the polyol (b1-1) and the polyisocyanate (b1-2) are not particularly limited and can be appropriately selected taking into consideration various conditions such as safety, quality, and cost. The reaction temperature is preferably 70 to 120°C, and the reaction time is preferably 30 minutes to 5 hours.

[0071] When reacting the polyol (b1-1) with the polyisocyanate (b1-2), a catalyst such as a tertiary amine catalyst or an organometallic catalyst may be used as necessary.

[0072] The reaction may be carried out in a solvent-free environment or in the presence of an organic solvent.

[0073] The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include ester-based solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; ketone-based solvents such as acetone, methyl ethyl ketone, methyl butyl ketone, and cyclohexanone; ether ester-based solvents such as methyl cellosolve acetate and butyl cellosolve acetate; aromatic hydrocarbon-based solvents such as toluene and xylene; and amide-based solvents such as dimethylformamide and dimethylacetamide. These may be used alone or in combination of two or more.

[0074] The organic solvent may be removed during the production of the polyurethane resin (b1) or after the production of the polyurethane (b1) by a suitable method such as heating under reduced pressure or drying at normal pressure.

[0075] The other components in the base layer are not particularly limited and can be appropriately selected within a range that does not impair the properties of the adhesive tape, and examples thereof include tackifier resins, polymer components other than the material of the base layer, crosslinking agents, antiaging agents, UV absorbers, fillers, polymerization inhibitors, surface conditioners, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, additives such as organic pigments, inorganic pigments, pigment dispersants, silica beads, and organic beads, and inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconia, and antimony pentoxide. These may be used alone or in combination of two or more. The content of other components in the base layer can be appropriately selected within a range that does not impair the properties of the adhesive tape.

[0076] The tackifier resin can be used for the purpose of increasing the adhesion between the adhesive layer of the adhesive tape and the base layer, and increasing the heat resistance.

[0077] The tackifier resin is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the softening point is 80°C or higher, more preferably 90°C or higher, even more preferably 100°C or higher, and particularly preferably 110°C or higher.

[0078] As the tackifier resin, for example, those described in the section "rubber-based adhesive resin" below can be used, and the preferred embodiments are also the same.

[0079] The antiaging agent is not particularly limited and can be appropriately selected from known ones according to the purpose. For example, phenol-based antiaging agents, phosphorus-based antiaging agents (sometimes called "processing stabilizers"), amine-based antiaging agents, imidazole-based antiaging agents, etc. can be mentioned. These may be used alone or in combination of two or more. Among these, phenol-based antiaging agents and phosphorus-based antiaging agents are preferred, and using them in combination is preferred because it can effectively improve the heat resistance stability of the substrate material, and as a result, it is possible to obtain an adhesive tape that maintains good initial adhesion and has even better heat durability. In addition, since phosphorus-based antiaging agents may slightly discolor (yellowing) over time in a high-temperature environment, it is preferable to appropriately set the amount used in consideration of the balance between initial adhesion, heat durability, and discoloration prevention.

[0080] As the phenol-based antiaging agent, a phenol-based compound having a sterically hindered group can generally be used, and typical examples include monophenol type, bisphenol type, and polyphenol type. Specific examples include 2,6-di-t-butyl-4-methylphenol, 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4- ethyl-6-t-butylphenol), 4,4'-thiobis(6-t-butyl-3-methylphenol), 4,4'-butylidenebis-(3-methyl-6-t-butylphenol), Tetrakis-[methylene-3-(3'5'-di-t-butyl-4-hydroxyphenyl)propionate]methane, n-octadecyl-3-(4'-hydroxy-3'5'-di t-butylphenyl)propionate. These can be used alone. Alternatively, two or more of them may be used in combination.

[0081] The amount of the phenol-based anti-aging agent used is not particularly limited and can be appropriately selected depending on the purpose, but it is preferably used in the range of 0.1 parts by mass to 5 parts by mass per 100 parts by mass of the substrate material, and using it in the range of 0.5 parts by mass to 3 parts by mass can effectively improve the heat resistance stability of the substrate material, and as a result, an adhesive tape that maintains good initial adhesion and has even better heat durability can be obtained.

[0082] The adhesive layer in the present invention essentially contains an adhesive resin containing a tri-copolymer represented by the general formula (1) described below as a main component, a tackifier resin, and may contain a filler as required. The adhesive layer in the present invention is formed from an adhesive composition containing an adhesive resin containing a tri-copolymer represented by the general formula (1) described below as a main component, a tackifier resin, and a filler and / or other components added as required.

[0083] The stress of the adhesive layer at 25% elongation is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.04 MPa to 0.4 MPa, more preferably 0.05 MPa to 0.1 MPa. When the stress of the adhesive layer at 25% elongation is within the preferred range, the adhesive tape can have a suitable adhesive strength, and can be relatively easily peeled off even when stretched and peeled off. On the other hand, when the stress of the adhesive layer at 25% elongation is less than 0.04 MPa, the adhesive tape may peel off when a load is applied in the shear direction of the adhesive tape while fixing hard adherends to each other, and when it exceeds 0.4 MPa, the force required to stretch the adhesive tape when peeling off the adhesive tape may be excessive.

[0084] In this embodiment, the storage modulus G' (23°C) of the adhesive layer is 1.0 x 10 5 ~1.0×10 7 Pa is preferably 1.0×10 5 ~1.0×10 6 Pa is more preferably 1.5×10 5 ~9.0×10 5 More preferably, the temperature is 2.0×10 Pa. 5 ~8.0×10 5 It is even more preferable that the storage modulus G' (23°C) of the adhesive layer is in the above range, which has the effect of achieving a high degree of initial adhesion, high load retention, and removability over time. In addition, by having the breaking stress of the adhesive layer in the above range, it becomes easy to follow the distortion of the adherend and to obtain excellent adhesive strength, and the dimensional stability of the base layer can be ensured, so that suitable application workability can be obtained.

[0085] The stress of the adhesive layer at 25% elongation refers to the stress value measured when the adhesive layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and pulled in the length direction at a tensile speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH, and elongated by 25%.

[0086] The breaking stress of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.6 to 5.0 MPa, more preferably 1.0 to 4.0 MPa. When the breaking stress of the adhesive layer is within the above-mentioned preferred range, the adhesive tape can be prevented from tearing even when the adhesive tape is stretched and peeled off, and the load for stretching the adhesive tape is not excessive, so that the peeling operation is easy. On the other hand, when the breaking stress of the adhesive layer is less than 0.6 MPa, adhesive residue may occur due to cohesive failure of the adhesive layer when the adhesive tape is stretched and peeled off, and when it exceeds 5.0 MPa, sufficient adhesiveness may not be obtained. The force required to stretch and deform the adhesive tape also depends on the thickness of the adhesive tape. For example, even when an adhesive tape with a thick thickness and high breaking stress is stretched and peeled off, it may not be stretched sufficiently and cannot be peeled off.

[0087] The breaking stress of the adhesive layer refers to the stress value measured when the adhesive layer is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and pulled in the lengthwise direction at a tensile speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH, until the adhesive layer breaks.

[0088] The breaking elongation of the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 450 to 1300%, more preferably 500 to 1200%, and even more preferably 600 to 1100%. When the breaking elongation of the adhesive layer is within the above-mentioned preferred range, it is possible to achieve both suitable adhesion and removability (ease of peeling).

[0089] The breaking elongation of the adhesive layer refers to the tensile elongation measured when the adhesive layer was punched out into a dumbbell shape with a gauge length of 20 mm and a width of 10 mm, and pulled in the length direction at a tensile speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH, until breaking.

[0090] The average thickness of the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 to 200 μm, more preferably 10 to 150 μm, even more preferably 30 to 120 μm, and particularly preferably 40 μm to 100 μm. The "average thickness of the adhesive layer" means the thickness of the adhesive layer on one side of the adhesive tape. When the adhesive tape has adhesive layers on both sides, the average thickness of the adhesive layer on one side and the average thickness of the adhesive layer on the other side may be the same or different, but are preferably the same thickness.

[0091] In this specification, the average thickness of the adhesive layer can be measured by the following method. That is, after immersing the adhesive tape in liquid nitrogen for 1 minute, the adhesive tape is folded and split in the liquid nitrogen using tweezers along the width direction to prepare a slice for observing the cut surface in the thickness direction of the adhesive tape. After the slice is returned to room temperature in a desiccator, it is fixed to a sample stage so that an electron beam is incident perpendicularly to the cut surface, and the cut surface is observed using an electron microscope. Based on the scale of the electron microscope, the thickness of the adhesive layer in the adhesive tape is measured at 10 points, and the arithmetic average value is taken as the thickness of the adhesive layer. The thickness of the adhesive layer is the length measured along the lamination direction from one surface to the other surface.

[0092] The adhesive resin used in the adhesive layer of the present invention preferably contains a triblock copolymer represented by the following general formula (1) as a main component. In this specification, the "main component of the adhesive resin" refers to the main component of the resin components contained in the adhesive resin (typically, a component contained in an amount of more than 50 mass%). In addition, with respect to the entire adhesive resin used in the adhesive layer of the present invention, the triblock copolymer represented by the following general formula (1) preferably accounts for 30 to 100 mass%, and more preferably the triblock copolymer represented by the above general formula (1) accounts for 50 to 95 mass%.

[0093] In the adhesive layer of the present invention, when the content of the triblock copolymer is 30 to 100% by mass, it is easy to achieve both high load holding power and adhesive strength.

[0094] The adhesive resin in the present invention is represented by the general formula (1): [ka] (In the above general formula (1), A, B, and C each independently represent a repeating unit, A and C each independently represent a methacrylic acid alkyl ester monomer unit, B represents an acrylic acid alkyl ester monomer unit, p, q, and r each independently represent the degree of polymerization of each monomer unit, and A and C may be methacrylic acid alkyl ester monomer units having the same or different chemical structures. In the above general formula (1), * represents a bond to another atom.)

[0095] The adhesive layer containing the triblock copolymer can ensure a relatively high elastic modulus, and therefore can easily ensure high load retention, removability over time, and adhesive strength with excellent storage stability. In particular, when the adhesive tape is pulled, if the adhesive layer contains a filler, the filler in the adhesive layer can be maintained exposed on the surface for a long period of time compared to a case in which the adhesive layer does not contain a filler, and thus a synergistic effect is exhibited in combination with the effect of the filler.

[0096] In the above general formula (1), A and C represent repeating units different from B, and represent methacrylic acid alkyl ester monomer units. A and C are each independent and may be the same methacrylic acid alkyl ester monomer units or methacrylic acid alkyl ester monomer units having different chemical structures. In this specification, the term "methacrylic acid alkyl ester monomer unit" refers to a structural unit derived from a methacrylic acid alkyl ester monomer when a methacrylic acid alkyl ester monomer is (co)polymerized or graft polymerized, that is, a repeating unit derived from a methacrylic acid ester monomer. In the present invention, the methacrylic acid alkyl ester monomer unit is represented by the following general formula (2): [ka] (In the above general formula (2), R 1 represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 2 may be substituted with, and the substituent R 2 represents a halogen atom, an amino group, or a cyano group. In the above general formula (2), R 1 From the viewpoints of removability and high load retention, the alkyl group is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and even more preferably an alkyl group having 1 or 2 carbon atoms.

[0097] In the above general formula (2), the alkyl group having 1 to 12 carbon atoms may be linear, branched, or cyclic, and from the viewpoint of adhesive strength, linear or branched is preferred, and linear is more preferred.

[0098] In the above general formula (2), examples of the alkyl group having 1 to 12 carbon atoms include linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, t-butyl, n-pentyl, isopentyl, hexyl, octyl, nonyl, decyl, undecyl, and dodecyl, as well as cyclic alkyl groups such as cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, dicyclopentanyl, and adamantyl. Among these, from the viewpoint of removability and high load retention, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, or t-butyl is preferred, and methyl, ethyl, and propyl are more preferred.

[0099] In the above general formula (2), examples of the alkyl group having 1 to 4 carbon atoms include linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, and t-butyl groups, as well as cyclic alkyl groups such as cyclobutyl groups. From the viewpoints of removability and high load retention, the alkyl group having 1 to 4 carbon atoms is preferably methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, or t-butyl, and more preferably methyl. Therefore, the preferred R in the above general formula (2) 1 is any one of an alkyl group, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, or a cyclobutyl group, and one or more hydrogen atoms in the alkyl group may be substituted with a halogen atom, an amino group, a cyano group, a linear or branched alkyl group (a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, an isopentyl group, a hexyl group, an octyl group, a nonyl group, a decyl group, or an undecyl group or a dodecyl group), or a cyclic alkyl group (a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, a cyclodecyl group, a dicyclopentanyl group, or an adamantyl group).

[0100] In the present embodiment, for example, the methacrylic acid alkyl ester monomer is not particularly limited and includes methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, t-butyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, pentadecyl methacrylate, cyclohexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, 2-hexyldecyl methacrylate, etc. Among these, methyl methacrylate is preferred from the viewpoints of high load retention and dismantling ability.

[0101] In the above general formula (1), B represents a repeating unit different from A and C, and represents an alkyl acrylate monomer unit. In this specification, the term "alkyl acrylate monomer unit" refers to a structural unit derived from an alkyl acrylate monomer when an alkyl acrylate monomer is (co)polymerized or graft polymerized, i.e., a repeating unit derived from an acrylate monomer. In the present invention, the alkyl acrylate monomer unit is represented by the following general formula (3): [ka] (In the above general formula (3), R 3 represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 4 may be substituted with, and the substituent R 4 represents a halogen atom, an amino group, or a cyano group. In the above general formula (3), R 3 From the viewpoint of adhesion, an alkyl group having 1 to 12 carbon atoms is more preferable, and an alkyl group having 4 to 8 carbon atoms is even more preferable.

[0102] In the above general formula (3), the alkyl group having 1 to 12 carbon atoms may be linear, branched, or cyclic, and from the viewpoint of adhesiveness, linear or branched is preferable. Examples of the alkyl group having 1 to 12 carbon atoms are the same as the examples of the alkyl group having 1 to 12 carbon atoms in the above general formula (2).

[0103] Therefore, the preferred R in the above general formula (3) 3 represents a linear or branched alkyl group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, an isopentyl group, a hexyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, or a dodecyl group, or a cyclic alkyl group such as a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, a cyclodecyl group, a dicyclopentanyl group, or an adamantyl group, and one or more hydrogen atoms in the alkyl group may be substituted with a halogen atom, an amino group, or a cyano group.

[0104] In this embodiment, examples of the acrylic acid alkyl ester monomer include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, t-butyl acrylate, amyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, etc. Among these, from the viewpoint of achieving both adhesive strength and removability, n-butyl acrylate, 2-ethylhexyl acrylate, and copolymers thereof are preferred.

[0105] In the above general formula (1), p, q, and r each independently represent the degree of polymerization of each monomer unit. The values ​​of p, q, and r relate to the molecular weight, etc. p / (p+q+r) is preferably 0.02 to 0.40, and more preferably 0.05 to 0.37. q r / (p+q+r) is preferably 0.20 to 0.95, and more preferably 0.25 to 0.90. r / (p+q+r) is preferably 0.02 to 0.40. It is preferable that the ratio is 0.05 to 0.37.

[0106] In this embodiment, the triblock copolymer has the following general formula (4): [ka] (In the above general formula (4), R 1 and R 5 each independently represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 2 may be substituted with, and the substituent R 2 represents a halogen atom, an amino group, or a cyano group; R 3 represents an alkyl group having 1 to 20 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 4 may be substituted with, and the substituent R 4 represents a halogen atom, an amino group, a cyano group, or an alkyl group having 1 to 20 carbon atoms, and p, q, and r each independently represent the degree of polymerization of the respective monomer units.

[0107] In the above general formula (4), R 1 is R in the above general formula (2). 1 In the above general formula (4), R 3 is R in the above general formula (3). 3 In the above general formula (4), R 5 is R in the above general formula (2). 1 In the above general formula (4), p, q, and r can be the same as p, q, and r in the above general formula (1). 1 and R 5 may be the same or different.

[0108] In this embodiment, when the triblock copolymer is represented by the above general formula (4), R 1 is preferably selected from the group consisting of linear or branched alkyl groups such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, and t-butyl, and a cyclobutyl group; R 3 is preferably selected from the group consisting of methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, t-butyl, n-pentyl, isopentyl, hexyl, octyl, nonyl, decyl, and undecyl groups; R 5 is preferably selected from the group consisting of linear or branched alkyl groups, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, and the like, and a cyclobutyl group, and it is preferable that p / (p+q+r) is 0.02 to 0.40, q / (p+q+r) is 0.20 to 0.95, and r / (p+q+r) is 0.02 to 0.40.

[0109] In the triblock copolymer of the present invention, it is preferable that A and C in the general formula (1) are the same. Specifically, when the triblock copolymer has a repeating unit represented by the above general formula (4), R 1 and R 5 and are the same group, p / (p+q+r) is 0.02 to 0.40, q / (p+q+r) is 0.20 to 0.95, and r / (p+q+r) is 0.02 to 0.40.

[0110] In a triblock copolymer having a repeating unit represented by the above general formula (1), when A and C are the same (ABA type triblock copolymer), a higher elastic modulus can be ensured, and therefore it is easier to ensure adhesive strength with excellent high load retention, removability over time, and storage stability.

[0111] In this embodiment, the triblock copolymer preferably has a weight average molecular weight Mw of 50,000 to 300,000 and a number average molecular weight Mn of 50,000 to 300,000. More preferably, the triblock copolymer has a weight average molecular weight Mw of 100,000 to 250,000 and a number average molecular weight Mn of 100,000 to 250,000, and even more preferably, the triblock copolymer has a weight average molecular weight Mw of 130,000 to 230,000 and a number average molecular weight Mn of 130,000 to 230,000.

[0112] It is preferable for the weight average molecular weight Mw of the triblock copolymer to be within the above range from the viewpoint of achieving both adhesion, removability and high load retention, and it is preferable for the number average molecular weight Mn of the triblock copolymer to be within the above range from the viewpoint of achieving both adhesion, removability and high load retention.

[0113] Here, the weight average molecular weight M of the triblock polymer by GPC method is W and number average molecular weight M N The measurement is performed using a GPC apparatus (HLC-8329GPC, manufactured by Tosoh Corporation) and is expressed as a standard polystyrene equivalent value. The measurement conditions are as follows. [Measurement conditions] Sample concentration: 0.5% by mass (tetrahydrofuran (THF) solution) Sample injection volume: 100μL · Eluent: THF · Flow rate: 1.0mL / min · Measurement temperature: 40℃ - Column: TSKgel GMHHR-H(20) x 2 Guard column: TSKgel HXL-H Detector: Differential refractometer Standard polystyrene molecular weight: 10,000 to 20 million (Tosoh Corporation)

[0114] The triblock copolymer according to the present invention and / or a partial structure (e.g., a block) of the triblock copolymer preferably has stereoregularity (tacticity). Specifically, the triblock copolymer according to the present invention and / or a partial structure (e.g., a block) of the triblock copolymer may have any of isotactic, syndiotactic, and atactic stereoregularity, or may have a plurality of blocks having any of these stereoregularities.

[0115] A preferred embodiment of the triblock copolymer in the present invention is the triblock copolymer represented by the general formula (1) p The syndiotacticity of the polymer block in the -" portion preferably exhibits a ratio of rr triads of 65% or more, and more preferably the ratio of rr triads is 75 to 95%. A preferred embodiment of the triblock copolymer in the present invention is the "-(C)" in general formula (1). r The syndiotacticity of the polymer block in the -" portion preferably exhibits a ratio of rr triads of 65% or more, and more preferably the ratio of rr triads is 75 to 95%. A preferred embodiment of the triblock copolymer in the present invention is the "-(B)" in the general formula (1). r The polymer block of the "-" portion preferably exhibits atacticity.

[0116] The triblock copolymer of the present invention has a ratio of rr triads of 65% or more "-(A) p When the composition contains a polymer block of the -" portion, the effect of providing good removability and holding power at high temperatures is achieved.

[0117] Generally, the syndiotacticity of a polymer is expressed by the ratio of a chain (triad) consisting of three monomer units that is rr. In this specification, it is calculated by NMR measurement of the polymer. Specifically, 13The signal peaks that represent the arrangement of triads in C-NMR vary depending on the conditions such as the type of polymer, the measurement solvent, and the measurement temperature, so it is necessary to identify and quantify the signals according to the respective measurement conditions. In this specification, the samples dissolved in deuterated chloroform are measured at 50°C.

[0118] Preferred forms of the triblock copolymer in the present invention include polymethyl methacrylate block-polyn-butyl acrylate block-polymethyl methacrylate, polyethyl methacrylate block-polyn-butyl acrylate block-polyethyl methacrylate, polypropyl methacrylate block-polyn-butyl acrylate block-polypropyl methacrylate, polymethyl methacrylate block-polyt-butyl acrylate block-polymethyl methacrylate, and polymethyl methacrylate block-polypropyl acrylate block-polymethyl methacrylate.

[0119] The triblock copolymer of the present invention has an overall molecular weight distribution, in terms of the ratio of weight average molecular weight / number average molecular weight, preferably in the range of 1.0 to 2.3, more preferably in the range of 1.00 to 1.50.

[0120] In the present embodiment, when A and C in the general formula (1) are different repeating units, the "-(A) p Total weight of polymer blocks of "-" part (relevant "-(A)" p The total weight of the polymer blocks of "-" is referred to as a.) and "-(B) q Total weight of polymer blocks of "-" part (said "-(B) q The total weight of the polymer blocks in the -" portion is referred to as b. From the viewpoint of adhesive properties, the mass ratio of a / b is preferably within the range of 2 / 98 to 67 / 33, and more preferably within the range of 5 / 95 to 60 / 40. In the present embodiment, when A and C in the general formula (1) are different repeating units, the "-(C)" contained in the molecule of the triblock copolymer of the present invention r Total weight of polymer blocks of "-" part (relevant "-(C)" p The total weight of the polymer blocks of "-" is referred to as c. q The ratio of the "-" portion to the total weight of the polymer blocks, c / b, is preferably within the range of 2 / 98 to 67 / 33, and more preferably within the range of 5 / 95 to 60 / 40, from the viewpoint of adhesive properties.

[0121] In the present embodiment, when A and C in the general formula (1) are the same repeating unit, the "-(A)" contained in the molecule of the triblock copolymer of the present invention p The polymer block of the -" portion and the -(C) r - Total weight of polymer blocks in "-(A)" p The polymer block of the -" portion and the -(C) r The total weight of the polymer blocks of "-" is referred to as d.) and "-(B) q From the viewpoint of adhesive properties, the ratio of the "-" portion to the total weight of the polymer blocks (referred to as b) is preferably within the range of 5 / 95 to 80 / 20, and more preferably within the range of 10 / 90 to 75 / 25, in terms of the mass ratio d / b.

[0122] The triblock copolymer in the present invention may be modified, if necessary, with a functional group such as a hydroxyl group, a carboxyl group, an acid anhydride group, an amino group, or a trimethoxysilyl group in the molecular side chain or at the molecular main chain terminal, as long as the effect of the present invention is not impaired.

[0123] The method for producing the triblock copolymer used in this embodiment is not particularly limited and can be appropriately selected from conventionally known production methods, for example, a method for sequentially polymerizing a block copolymer by an anionic living polymerization method, a cationic living polymerization method, etc. In addition, when the triblock copolymer used in this embodiment has stereoregularity (for example, syndiotacticity), a known method using an organometallic complex may be used.

[0124] As an example of a method for producing the triblock copolymer of the present invention, a triblock copolymer can be produced by a technique comprising sequentially polymerizing a methacrylic acid alkyl ester monomer as a main component and a monomer mainly composed of an acrylic acid alkyl ester monomer and / or a methacrylic acid alkyl ester monomer as a main component in an inert polymerization solvent using a polymerization initiator so as to obtain a desired block bonding order.

[0125] As a more specific embodiment of the method for producing a triblock copolymer, first, a methacrylic acid alkyl ester monomer is polymerized in a polymerization solvent using a polymerization initiator by an anionic living polymerization method to obtain a polymethacrylic acid alkyl ester block having a living active terminal ("-(A)" in general formula (1) p Secondly, an alkyl methacrylate-alkyl acrylate diblock copolymer having a living active end (corresponding to the "-(A)" portion in general formula (1)) is formed by polymerizing an alkyl acrylate monomer from the living active end of the polyalkyl methacrylate. p -(B) q Thirdly, a part of the alkyl methacrylate-alkyl acrylate diblock copolymer having a living active end is reacted with a coupling agent to obtain a coupled alkyl methacrylate-alkyl acrylate-alkyl methacrylate triblock copolymer (corresponding to the "-(A)" part of general formula (1)). p -(B) q -(C) r― In this case, the polymerization is terminated by reacting with a polymerization terminator such as alcohol, if necessary.

[0126] Examples of the polymerization initiator include organolithium compounds and organometallic compounds such as organolithium compounds and organometallic complexes.

[0127] Examples of the organometallic complex include rare earth metal complexes having a pentamethylcyclopentadienyl group as a ligand, such as bis(pentamethylcyclopentadienyl)samarium methyltetrahydrofuranate, bis(pentamethylcyclopentadienyl)yttrium methyltetrahydrofuranate, etc. Furthermore, these organometallic complexes may be used in combination with alkylaluminums such as trimethylaluminum.

[0128] Examples of the organolithium compound include alkyllithium such as t-butyllithium, and compounds obtained by reacting alkyllithium with 1,1-diphenylethylene, diphenylmethane, etc. Furthermore, these organolithium compounds may be used in combination with inorganic salts such as lithium chloride, lithium salts of alkoxides such as lithium 2-(2-methoxyethoxy)ethoxide, and organoaluminum compounds such as diisobutyl(2,6-di-t-butyl-4-methylphenoxy)aluminum.

[0129] Examples of the polymerization solvent that can be used include hydrocarbon solvents such as benzene, toluene, and xylene; halogenated hydrocarbon solvents such as chloroform, methylene chloride, and carbon tetrachloride; and ether solvents such as tetrahydrofuran and diethyl ether.

[0130] The adhesive resin used in the adhesive layer in the present invention contains a triblock copolymer represented by the above general formula (1) as a main component, and resins other than the triblock copolymer represented by the above general formula (1) are not particularly limited and include diblock copolymers, acrylic adhesive resins, and rubber-based adhesive resins.

[0131] The adhesive resin in the present invention is represented by the general formula (5): [ka] (In the above general formula (5), D and E each independently represent a repeating unit, D represents a methacrylic acid alkyl ester monomer unit, E represents an acrylic acid alkyl ester monomer unit, and s and t each independently represent the degree of polymerization of each monomer unit. In the above general formula (5), * represents a bond to another atom.)

[0132] In this embodiment, when a triblock copolymer and a diblock copolymer are used in combination in the adhesive resin, it becomes easier to ensure high elastic modulus and initial adhesion, so that it becomes easier to ensure high load retention, removability over time, and initial adhesion. In particular, when the adhesive layer contains a filler, when the adhesive tape is pulled, the filler in the adhesive layer can be maintained exposed to the surface for a long period of time compared to a form in which the filler is not present in the adhesive layer, and thus an excellent synergistic effect is exhibited in combination with the effect of the filler.

[0133] The methacrylic acid alkyl ester monomer unit and the acrylic acid alkyl ester monomer unit in the above general formula (5) can have the same form as the methacrylic acid alkyl ester monomer unit and the acrylic acid alkyl ester monomer unit in the above general formula (1).

[0134] The diblock polymer in the present invention is represented by the following general formula (6): [ka] (In the above general formula (6), R 6 represents an alkyl group having 1 to 12 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 8 may be substituted with, and the substituent R 8 represents a halogen atom, an amino group, or a cyano group; R 7represents an alkyl group having 1 to 20 carbon atoms, and one or more hydrogen atoms in the alkyl group are each independently selected from the group consisting of a substituent R 9 may be substituted with, and the substituent R 9 represents a halogen atom, an amino group, a cyano group, or an alkyl group having 1 to 20 carbon atoms, and s and t each independently represent the degree of polymerization of each monomer unit.

[0135] In the above general formula (6), R 6 is R in the above general formula (2). 1 In the above general formula (6), R 7 is R in the above general formula (3). 3 In the above general formula (6), s and t can have the same configuration as p and q in the above general formula (1).

[0136] In this embodiment, the diblock copolymer preferably has a weight average molecular weight Mw of 50,000 to 300,000 and a number average molecular weight Mn of 50,000 to 300,000. The weight average molecular weight can be measured using the method for measuring the weight average molecular weight of the triblock copolymer in the present invention.

[0137] In the above general formula (6), p, q, and r each independently represent the degree of polymerization of each monomer unit. The values ​​of s and t relate to the molecular weight, etc. s / (s+t) is preferably 0.01 to 0.99, and more preferably 0.1 to 0.9. t / (s+t) is preferably 0.01 to 0.99, and more preferably 0.1 to 0.9.

[0138] In this embodiment, the content of the diblock copolymer is not particularly limited and can be appropriately selected depending on the purpose. In this embodiment, the diblock copolymer is preferably contained in an amount of 0 to 100 parts by mass, more preferably 1 to 50 parts by mass, and even more preferably 10 to 50 parts by mass, relative to 100 parts by mass of the triblock copolymer. When the content of the tackifier resin in the adhesive layer is within the above range, adhesion to the adherend is easily ensured.

[0139] The acrylic adhesive resin is not particularly limited and can be appropriately selected depending on the purpose. For example, it may contain an acrylic polymer and, if necessary, additives such as a tackifier resin and a crosslinking agent.

[0140] The acrylic polymer has a chemical structure other than that of the triblock copolymer represented by the general formula (1) above, and can be produced, for example, by polymerizing a (meth)acrylate monomer.

[0141] As the (meth)acrylate monomer, for example, an alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms can be used.

[0142] Specific examples of alkyl (meth)acrylates having an alkyl group having 1 to 12 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0143] As the alkyl (meth)acrylate having an alkyl group with 1 to 12 carbon atoms, it is preferable to use an alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms, it is more preferable to use an alkyl (meth)acrylate having an alkyl group with 4 to 8 carbon atoms, and it is particularly preferable to use n-butyl acrylate in order to ensure excellent adhesion to the adherend.

[0144] The alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms is preferably used in the range of 0 to 50 mass %, and more preferably 0 to 30 mass %, based on the total amount of monomers used in the production of the acrylic polymer.

[0145] As the monomers usable in the production of the acrylic polymer, in addition to the above-mentioned ones, highly polar vinyl monomers can be used as necessary.

[0146] Examples of highly polar vinyl monomers include (meth)acrylic monomers such as (meth)acrylic monomers having a hydroxyl group, (meth)acrylic monomers having a carboxyl group, and (meth)acrylic monomers having an amide group, as well as sulfonic acid group-containing monomers such as vinyl acetate, ethylene oxide-modified succinic acid acrylate, and 2-acrylamido-2-methylpropanesulfonic acid. These may be used alone or in combination of two or more.

[0147] Specific examples of vinyl monomers having a hydroxyl group include (meth)acrylic monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate.

[0148] It is preferable to use a vinyl monomer having a hydroxyl group when an adhesive resin containing an isocyanate-based crosslinking agent is used. Specifically, it is preferable to use 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, or 6-hydroxyhexyl (meth)acrylate as the vinyl monomer having a hydroxyl group.

[0149] The vinyl monomer having a hydroxyl group is preferably used in an amount of 0.01 to 1.0 mass %, more preferably 0.03 to 0.3 mass %, based on the total amount of monomers used in the production of the acrylic polymer.

[0150] Specific examples of vinyl monomers having a carboxyl group include (meth)acrylic monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, (meth)acrylic acid dimer, crotonic acid, and ethylene oxide-modified succinic acid acrylate. Among these, acrylic acid is preferred.

[0151] Specific examples of vinyl having an amide group include (meth)acrylic monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, acrylamide, and N,N-dimethylacrylamide.

[0152] The highly polar vinyl monomer is preferably used in the range of 1.5 to 20 mass % relative to the total amount of monomers used in the production of the acrylic polymer, more preferably in the range of 1.5 to 10 mass %, and even more preferably in the range of 2 to 8 mass %, since this allows the formation of an adhesive layer that is well balanced in terms of cohesive strength, holding power, and adhesiveness.

[0153] The method for producing the acrylic polymer is not particularly limited and may be appropriately selected from known methods depending on the purpose, and examples thereof include a method in which a monomer is polymerized by a polymerization method such as a solution polymerization method, a bulk polymerization method, a suspension polymerization method, an emulsion polymerization method, etc. Among these, it is preferable to produce the acrylic polymer by the solution polymerization method or the bulk polymerization method.

[0154] During polymerization, if necessary, a peroxide-based thermal polymerization initiator such as benzoyl peroxide or lauroyl peroxide, an azo thermal polymerization initiator such as azobisisobutylnitrile, an acetophenone-based photopolymerization initiator, a benzoin ether-based photopolymerization initiator, a benzyl ketal-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a benzoin-based photopolymerization initiator, a benzophenone-based photopolymerization initiator, or the like can be used.

[0155] The weight-average molecular weight of the acrylic polymer obtained by the above method is preferably 300,000 to 3,000,000, and more preferably 500,000 to 2,500,000, as measured in terms of standard polystyrene using gel permeation chromatography (GPC) under the same method and conditions as those for the triblock copolymer.

[0156] With respect to the total adhesive resin used in the adhesive layer of the present invention, the acrylic adhesive resin preferably accounts for 0 to 50 mass %, and more preferably 0 to 30 mass %.

[0157] In the pressure-sensitive adhesive layer of the present invention, when the content of the acrylic pressure-sensitive adhesive resin is within the above range, it is easy to achieve both adhesiveness, removability over time, and high load holding power.

[0158] The rubber-based adhesive resin is not particularly limited, and examples thereof include rubber materials that can generally be used as adhesive resins, such as synthetic rubber-based adhesive resins and natural rubber-based adhesive resins, and those that contain additives such as tackifier resins as necessary.

[0159] Examples of rubber materials include block copolymers of aromatic vinyl compounds and conjugated diene compounds, specifically styrene-based resins such as styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, styrene-isoprene-butadiene-styrene copolymers, styrene-butadiene-styrene copolymers, styrene-ethylene-butylene copolymers, styrene-ethylene-propylene copolymers, and hydrogenated products thereof. These may be used alone or in combination of two or more. Among these, it is more preferable to use two or more styrene-based resins in combination because it can provide the adhesive tape with excellent adhesive properties and holding power, and it is particularly preferable to use a combination of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer.

[0160] The styrene resin may be a single structure such as a linear structure, a branched structure, or a multi-branched structure, or may be a mixture of different structures. When a styrene resin rich in linear structures is used in the adhesive layer, it can provide excellent adhesive performance to the adhesive tape. On the other hand, a branched or multi-branched structure in which a styrene block is arranged at the molecular end can have a pseudo-crosslinked structure and can provide excellent cohesive force, so that it can provide high holding power. For this reason, it is preferable to use a mixture of styrene resins according to the required characteristics.

[0161] The styrene resin used preferably contains 10 to 80 mass % of the structural unit represented by the following chemical formula (B) relative to the total mass of the styrene resin, more preferably 12 to 60 mass %, even more preferably 15 to 40 mass %, and particularly preferably 17 to 35 mass %, which allows excellent adhesion and heat resistance to be obtained. [ka]

[0162] With respect to the total adhesive resin used in the adhesive layer of the present invention, the rubber-based adhesive resin preferably accounts for 0 to 50 mass %, and more preferably 0 to 30 mass %.

[0163] In the adhesive layer of the present invention, when the content of the rubber-based adhesive resin is within the above range, it is easy to achieve both adhesiveness, dismantling ability, and high load retaining strength.

[0164] The adhesive layer of the present embodiment contains a tackifier resin. The tackifier resin is preferably used to improve the adhesion to the adherend and the surface adhesive strength.

[0165] The tackifier resin of the present embodiment preferably has a softening point of 95° C. or higher. More preferably, the softening point is 95° C. to 180° C., and more preferably, 95° C. to 140° C., in order to form an adhesive layer with high adhesive performance. When a (meth)acrylate-based tackifier resin is used, the glass transition temperature is preferably 30° C. to 200° C., and more preferably, 50° C. to 160° C.

[0166] As the tackifier resin, a tackifier resin having a softening point (softening temperature) of 95° C. or more can be preferably used. By using an adhesive layer containing a tackifier resin having a softening point equal to or higher than the above-mentioned lower limit, an adhesive tape having better adhesive strength can be realized. Among the tackifier resins exemplified above, terpene-based tackifier resins (e.g., terpene-modified phenolic resins) and rosin-based tackifier resins (e.g., esterified products of polymerized rosin) having the above-mentioned softening points can be preferably used. The upper limit of the softening point of the tackifier resin is not particularly limited, and can be, for example, about 200° C. or less. The softening point of the tackifier resin is defined here as a value measured by the softening point test method (ring and ball method) specified in either JIS K 5902 or JIS K 2207.

[0167] The amount of the tackifier resin used is not particularly limited and can be appropriately selected depending on the purpose. In this embodiment, the tackifier resin is preferably contained in an amount of 10 to 75 parts by mass, more preferably 20 to 60 parts by mass, and even more preferably 30 to 50 parts by mass, relative to 100 parts by mass of the triblock copolymer. When the content of the tackifier resin in the adhesive layer is within the above range, adhesion to the adherend is easily ensured.

[0168] In this embodiment, the product of the softening point temperature [°C] of the tackifier resin and the amount of the tackifier resin added (the amount of the tackifier resin added when the triblock copolymer is taken as 100 parts by mass) is preferably 1,300 to 13,000.

[0169] When the product of the softening point (temperature) of the tackifier resin and the amount of the tackifier resin added is large, an adhesive layer having excellent heat resistance can be formed, and therefore an adhesive tape having excellent adhesion such as removability over time or storage stability can be provided. However, when the function is exerted at a temperature above the softening point, the workability decreases. Therefore, by setting the product of the softening point (temperature) of the tackifier resin and the amount of the tackifier resin added within the above range, an adhesive layer having excellent heat resistance can be formed while maintaining a certain level of workability. The value of the product (temperature of the softening point of the tackifier resin [°C] × amount of the tackifier resin added (amount of the tackifier resin added when the triblock copolymer is 100 parts by mass)) is more preferably 5000 to 13000, and even more preferably 6500 to 10000. When two or more types of tackifier resins are contained, it is preferable that the sum of the products of the softening point temperatures [°C] of each tackifier resin and the amount of each tackifier resin added (the amount of the tackifier resin added when the triblock copolymer is 100 parts by mass) is within the above-mentioned range.

[0170] Specific examples of the tackifier resin include rosin-based tackifier resins, polymerized rosin-based tackifier resins, polymerized rosin ester-based tackifier resins, rosin phenol-based tackifier resins, stabilized rosin ester-based tackifier resins, disproportionated rosin ester-based tackifier resins, hydrogenated rosin ester-based tackifier resins, terpene-based tackifier resins, terpene phenol-based tackifier resins, petroleum resin-based tackifier resins, and (meth)acrylate-based tackifier resins. These may be used alone or in combination of two or more. Among these, the tackifier resin is preferably a polymerized rosin ester-based tackifier resin, a rosin phenol-based tackifier resin, a disproportionated rosin ester-based tackifier resin, a hydrogenated rosin ester-based tackifier resin, a terpene phenol-based resin, or a (meth)acrylate-based resin.

[0171] Specific examples of the rosin-based tackifying resin include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins obtained by modifying these unmodified rosins through hydrogenation, disproportionation, polymerization, etc. (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc.; the same applies below); and various other rosin derivatives. Examples of the rosin derivative include rosin esters such as those obtained by esterifying unmodified rosin with alcohols (i.e., esterified products of rosin) and those obtained by esterifying modified rosin with alcohols (i.e., esterified products of modified rosin); unsaturated fatty acid modified rosins obtained by modifying unmodified rosin or modified rosin with unsaturated fatty acid; unsaturated fatty acid modified rosin esters obtained by modifying rosin esters with unsaturated fatty acid; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin, unsaturated fatty acid modified rosins, or unsaturated fatty acid modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; rosin phenolic resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) with an acid catalyst and thermally polymerizing the resulting mixture; and the like. When an acrylic polymer is used as the base polymer, it is preferable to use a rosin-based tackifier resin. From the viewpoint of improving adhesive properties such as adhesive strength, it is more preferable to use two or more kinds of the above rosin-based tackifier resins that are different in type, properties (eg, softening point), etc. in combination.

[0172] Examples of the terpene-based tackifying resin include terpene resins such as α-pinene polymer, β-pinene polymer, and dipentene polymer; modified terpene resins obtained by modifying these terpene resins (phenol-modified, aromatic-modified, hydrogen-modified, hydrocarbon-modified, etc.); and the like. Examples of the modified terpene resin include terpene-modified phenolic resin, styrene-modified terpene resin, aromatic-modified terpene resin, and hydrogen-modified terpene resin. When a acrylic polymer is used as the base polymer, it is preferable to use a terpene-based tackifying resin (e.g., terpene-modified phenolic resin). In particular, from the viewpoint of improving adhesive properties such as adhesive strength, it is preferable to use one or more of the above terpene-based tackifying resins (e.g., terpene-modified phenolic resins) that are different in type, characteristics (e.g., softening point) in combination.

[0173] Examples of hydrocarbon-based tackifying resins include various hydrocarbon resins such as aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone-indene resins.

[0174] As the adhesive resin containing the triblock copolymer of this embodiment, it is preferable to use one containing a crosslinking agent in order to further improve the cohesive strength of the adhesive layer.

[0175] The crosslinking agent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-based crosslinking agents, and aziridine-based crosslinking agents. These may be used alone or in combination of two or more. Among these, the crosslinking agent is preferably a type that is mixed after the production of the acrylic polymer and promotes a crosslinking reaction, and it is more preferable to use an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent that is highly reactive with the acrylic polymer.

[0176] Examples of the isocyanate crosslinking agent include tolylene diisocyanate, triphenylmethane isocyanate, naphthylene-1,5-diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and trimethylolpropane-modified tolylene diisocyanate. These may be used alone or in combination of two or more. Among these, trifunctional polyisocyanate compounds such as tolylene diisocyanate and its trimethylolpropane adduct, and triphenylmethane isocyanate are particularly preferred.

[0177] In this specification, the gel fraction value obtained by measuring the insoluble portion after immersing the adhesive layer in toluene for 24 hours is used as an index of the degree of crosslinking. The gel fraction of the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0 to 50% by mass, more preferably 0 to 20% by mass, and even more preferably 0 to 10% by mass in order to obtain an adhesive layer having both good cohesiveness and adhesiveness.

[0178] The gel fraction refers to a value measured by the following method. A pressure-sensitive adhesive composition containing a pressure-sensitive adhesive resin and, if necessary, additives is applied to a release sheet so that the thickness after drying is 50 μm, and the adhesive composition is dried at 100° C. for 3 minutes and aged at 40° C. for 2 days, and cut into a 50 mm square to be used as a sample. Next, the mass (G1) of the sample before immersion in toluene is measured in advance, and the toluene-insoluble portion of the sample after immersion in a toluene solution at 23° C. for 24 hours is separated by filtering with a 300 mesh wire net, and the mass (G2) of the residue after drying at 110° C. for 1 hour is measured, and the gel fraction is calculated according to the following formula (I). The mass (G3) of the conductive fine particles in the sample is calculated from the mass (G1) of the sample and the composition of the pressure-sensitive adhesive composition. Gel fraction (mass%) = (G2-G3) / (G1-G3) × 100 Formula (I)

[0179] Other components in the adhesive layer of the present embodiment are not particularly limited and can be appropriately selected within a range that does not impair the properties of the adhesive tape, and examples thereof include polymer components other than the adhesive resin, crosslinking agents, antiaging agents, ultraviolet absorbers, fillers, polymerization inhibitors, surface conditioners, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, plasticizers, softeners, flame retardants, metal deactivators, silica beads, organic beads, and other additives; silicon oxide, aluminum oxide, titanium oxide, zirconia, antimony pentoxide, and other inorganic fillers. These may be used alone or in combination of two or more.

[0180] The content of other components in the adhesive layer of the present embodiment can be appropriately selected within a range that does not impair the properties of the adhesive tape.

[0181] The adhesive layer of the adhesive tape of the present embodiment preferably contains a filler, a tackifier resin, and an adhesive resin containing as a main component a triblock copolymer represented by general formula (1).

[0182] In this embodiment, the adhesive composition, which is a precursor of the adhesive layer, preferably contains a filler. By including the filler in the adhesive composition, which is a precursor of the adhesive layer, the filler is exposed from the adhesive layer when the adhesive tape is stretched, thereby reducing the adhesion area between the adhesive layer and the adherend. Therefore, even if the stretching direction of the adhesive tape is at a relatively large angle, for example, a vertical direction (sometimes referred to as a "90° direction") with respect to the application surface of the adherend (hereinafter sometimes referred to as an "adhesive surface"), or even if the adhesive tape is stretched at a high speed, the adhesive tape can be peeled off more easily and quickly.

[0183] The type of the filler is not particularly limited and can be appropriately selected within a range that does not impair the effects of the present invention, and may be an inorganic filler or an organic filler. These may be used alone or in combination of two or more kinds.

[0184] Specific examples of the inorganic filler include aluminum hydroxide, magnesium hydroxide, aluminum oxide, silicon oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, iron oxide, silicon carbide, boron nitride, aluminum nitride, titanium nitride, silicon nitride, titanium boride, carbon, nickel, copper, aluminum, titanium, gold, silver, zirconium hydroxide, basic magnesium carbonate, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, tin oxide, tin oxide hydrate, borax, zinc borate, zinc metaborate, barium metaborate, zinc carbonate, magnesium-calcium carbonate, calcium carbonate, barium carbonate, Examples of such metals include molybdenum oxide, antimony oxide, red phosphorus, mica, clay, kaolin, talc, zeolite, wollastonite, smectite, silica (quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, ultrafine amorphous silica, etc.), potassium titanate, magnesium sulfate, sepiolite, zonolite, aluminum borate, barium sulfate, barium titanate, zirconia oxide, cerium, tin, indium, carbon, sulfur, cerium, cobalt, molybdenum, strontium, chromium, barium, lead, tin oxide, indium oxide, diamond, magnesium, platinum, zinc, manganese, and stainless steel. Among these, aluminum hydroxide and nickel are preferred.

[0185] The inorganic filler may be surface-treated, such as by silane coupling treatment or stearic acid treatment, in order to improve dispersibility in the adhesive resin.

[0186] Specific examples of the organic filler include polystyrene-based fillers, benzoguanamine-based fillers, polyethylene-based fillers, polypropylene-based fillers, silicone-based fillers, urea-formaldehyde-based fillers, styrene / methacrylic acid copolymers, fluorine-based fillers, acrylic-based fillers, polycarbonate-based fillers, polyurethane-based fillers, polyamide-based fillers, epoxy resin-based fillers, and thermosetting resin-based hollow fillers.

[0187] Among the above organic fillers, examples of silicone-based fillers that can be used include silicone rubber particles obtained by three-dimensionally crosslinking linear organopolysiloxanes (see JP-A-63-77942, JP-A-3-93834, and JP-A-04-198324), powdered silicone rubber (see U.S. Pat. No. 3,843,601, JP-A-62-270660, and JP-A-59-96,122), and the like.Furthermore, the surfaces of the silicone rubber particles obtained by the above method can be modified to have a (R'SiO 3 / 2 ) n Silicone composite particles (see JP-A-7-196815) can also be used that are coated with a silicone resin, which is a cured polyorganosilsesquioxane having a three-dimensional network-like crosslinked structure represented by the formula: (R' represents a substituted or unsubstituted monovalent hydrocarbon group).

[0188] As such silicone particles, those commercially available under the above-mentioned trade names, such as Trefil E-500, Trefil E-600, Trefil E-601, and Trefil E-850, are available from Dow Corning Toray Silicones Co., Ltd., and those commercially available under the above-mentioned trade names, such as KMP-600, KMP-601, KMP-602, and KMP-605, are available from Shin-Etsu Chemical Co., Ltd.

[0189] Another silicone-based filler that can be used is acrylic-modified silicone particles. Examples of the acrylic-modified silicone particles include emulsion graft polymers of polyorganosiloxane represented by the following general formula (C), acrylic acid ester monomers and / or methacrylic acid ester monomers, and functional group-containing monomers copolymerizable therewith. [ka] (In the above general formula (C), R 5 and R 6 each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms; 1 , X 2 , X 3 , X 4 , X 5, and X 6 each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group; Y 1 and Y 2 are each independently 1 or -[O-Si(X 7 )(X 8 )] c -X 9 represents a group represented by the formula: 7 , X 8 , and X 9 each independently represents a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group; X 1 , X 2 , X 3 , X 4 , X 5 , X 6 , X 7 , X 8 , and X 9 And Y 1 and Y 2 at least two groups in the formula (1) are hydroxyl groups, and a, b, and c each independently represent a positive number satisfying 0≦a≦1,000, 100≦b≦10,000, and 1≦c≦1,000.

[0190] In general formula (C), R 5 or R 6 The alkyl group having 1 to 20 carbon atoms represented by the formula (I) may be linear or branched, or may be cyclic. Specific examples include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, hexadecyl, octadecyl, cyclopentyl, cyclohexyl, and cycloheptyl. These alkyl groups may be substituted with a halogen atom, an acryloxy group, a methacryloxy group, a carboxy group, an alkoxy group, an alkenyloxy group, an amino group, or an alkyl, alkoxy, or (meth)acryloxy-substituted amino group.

[0191] R 5 or R 6 Examples of the aryl group having 6 to 20 carbon atoms represented by the formula (R) include a phenyl group, a tolyl group, and a naphthyl group. 5 or R 6 is preferably a methyl group.

[0192] In the general formula (C), X 1 ~X 9 As the alkyl group having 1 to 20 carbon atoms and the aryl group having 6 to 20 carbon atoms represented by the formula: 5 or R 6 The alkyl and aryl groups exemplified in X are the same as those exemplified in X. 1 ~X 9 Examples of the alkoxy group having 1 to 20 carbon atoms represented by the formula (I) include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a hexyloxy group, a heptyloxy group, an octyloxy group, a decyloxy group, and a tetradecyloxy group.

[0193] In the general formula (C), a, b, and c are positive numbers of 0≦a≦1,000, 100≦b≦10,000, and 1≦c≦1,000, but a is preferably a positive number of 0 to 200. If a is greater than 1,000, the strength of the resulting film is insufficient. b is preferably a positive number of 1,000 to 5,000. If b is less than 100, the film will have poor flexibility, and if it is greater than 10,000, it will be difficult to form a solid like particles. c is preferably a positive number of 1 to 200.

[0194] Moreover, the polyorganosiloxane represented by general formula (C) has at least two, and preferably 2 to 4, hydroxyl groups in one molecule from the viewpoint of crosslinkability, and the hydroxyl groups are preferably present at both ends of the molecular chain.

[0195] Examples of the acrylic acid ester monomer or methacrylic acid ester monomer include methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, and cyclohexyl methacrylate.

[0196] Examples of functional group-containing monomers copolymerizable with the above-mentioned acrylic acid ester monomers and / or methacrylic acid ester monomers include monomers having unsaturated bonds including carboxyl groups, amide groups, hydroxyl groups, vinyl groups, allyl groups, and the like.

[0197] The acrylic modified silicone powder is preferably obtained by mixing 100 parts by mass of polyorganosiloxane represented by the general formula (4) with 10 to 100 parts by mass of acrylic acid ester monomer and / or methacrylic acid ester monomer and 0.01 to 20 parts by mass of functional group-containing monomer copolymerizable therewith, and subjecting the mixture to emulsion graft polymerization. The conditions for emulsion graft polymerization are not particularly limited, and as the initiator used during polymerization, a known radical initiator normally used for acrylic polymers can be used. Also, as the emulsifier, a known anionic surfactant or nonionic surfactant can be used.

[0198] The acrylic-modified silicone particles are granulated and powdered by the following method. Examples include spray drying and airflow drying, but a spray dryer is preferred from the viewpoint of productivity. Powdering is preferably performed by hot drying at a temperature of 80 to 150°C.

[0199] As the acrylic modified silicone particles, for example, commercially available products such as Chaline R-170S and Chaline R-200 (both manufactured by Nissin Chemical Industry Co., Ltd.) can also be used.

[0200] The shape of the filler in this embodiment is not particularly limited and can be appropriately selected according to the purpose, and may be a regular shape or an irregular shape. Specific examples of the shape of the filler include polygonal, cubic, elliptical, spherical, needle-like, flat, and scaly shapes. Fillers of these shapes may be used alone or in combination of two or more. In addition, fillers of these shapes may be aggregated. Among these, the shape of the filler is preferably elliptical, spherical, or polygonal. When the filler shape is elliptical, spherical, polygonal, or the like, the adhesive layer slides well against the adherend when the adhesive tape is stretched, and the adhesive tape can be peeled off more easily and quickly.

[0201] The particle size distribution (D90 / D10) of the filler in this embodiment is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 2.5 to 20, and from the viewpoint of impact resistance, is more preferably 2.5 to 15, and is even more preferably 2.5 to 5. When the particle size distribution (D90 / D10) of the filler is within the preferred range, the adhesive tape can be peeled off more easily and quickly, is less likely to tear even when the thickness of the adhesive tape base is thin, and is excellent in impact resistance, shear adhesive strength, and split adhesive strength. On the other hand, when the particle size distribution (D90 / D10) of the filler is less than 2.5, the stretch peelability may be impaired, and when it exceeds 20, adhesive performance such as impact resistance, shear adhesive strength, and split adhesive strength may be impaired.

[0202] The particle size distribution (D90 / D10) of the filler in this embodiment can be obtained, for example, by measuring the average particle diameter of the filler using a measuring device (Microtrack) that uses a laser diffraction scattering method and converting it into a particle size distribution.

[0203] The average particle size of the filler in this embodiment is 0.1 to 40 μm, preferably 5 to 40 μm, more preferably 10 to 35 μm, even more preferably 10 to 30 μm, and particularly preferably 10 to 25 μm. When the average particle size of the filler is within the preferred range, the adhesive tape can be peeled off more easily and quickly, and even if the thickness of the adhesive tape base is thin, the adhesive tape is not easily torn, and has excellent impact resistance, shear adhesive strength, and split adhesive strength. On the other hand, when the particle size of the filler is less than 0.1 μm, the stretch peelability may be impaired, and when it exceeds 40 μm, adhesive performance such as impact resistance, shear adhesive strength, and split adhesive strength may be impaired.

[0204] The average particle size of the filler in this embodiment refers to the volume average particle size, and can be measured, for example, by using a measuring device (Microtrac) that uses a laser diffraction scattering method.

[0205] When the silicone rubber particles or silicone composite particles are used as the filler in this embodiment, the silicone rubber particles or silicone composite particles preferably have an average particle size of 0.1 to 40 μm, more preferably 5 to 40 μm. If the average particle size is less than 0.1 μm, the effect of reducing the adhesion area by the filler when the pressure-sensitive adhesive tape is stretched tends to decrease, and if it is more than 40 μm, the adhesive strength of the pressure-sensitive adhesive tape tends to decrease.

[0206] When the acrylic-modified silicone particles are used as the filler in this embodiment, the average particle size of the acrylic-modified silicone particles is preferably 0.1 to 40 μm, more preferably 5 to 40 μm, even more preferably 5 to 30 μm, and even more preferably 10 to 25 μm. If the average particle size is less than 0.1 μm, the effect of reducing the adhesion area by the filler when the pressure-sensitive adhesive tape is stretched tends to decrease, and if it is more than 40 μm, the adhesive strength of the pressure-sensitive adhesive tape tends to decrease.

[0207] The ratio of the average particle diameter of the filler in this embodiment to the average thickness of the adhesive layer is not particularly limited and can be appropriately selected depending on the purpose, but the ratio of the average particle diameter of the filler to the average thickness of the adhesive layer, expressed as [volume average particle diameter of the filler / average thickness of the adhesive layer], is preferably 5 / 100 or more, more preferably 5 / 100 to 95 / 100, even more preferably 10 / 100 to 75 / 100, and particularly preferably 20 / 100 to 60 / 100. When the ratio is 5 / 100 or more, the adhesive tape can be peeled off more easily and quickly, and even if the thickness of the adhesive tape base material is thin, it is difficult to tear. In addition, a ratio of 95 / 100 or less is advantageous in that the adhesive performance such as impact resistance, shear adhesive strength, and split adhesive strength is also more excellent.

[0208] The content of the filler in the adhesive layer of the present embodiment is preferably 0 to 300% by mass, more preferably 1 to 100% by mass, more preferably 10 to 60% by mass, and even more preferably 20 to 50% by mass, based on 100% by mass of the adhesive resin. By having the content of the filler be 1% by mass or more based on 100% by mass of the adhesive resin, the adhesive tape can be peeled off more easily and quickly. In addition, by having the content of the filler be 100% by mass or less based on 100% by mass of the adhesive resin, it is possible to prevent the adhesive composition from remaining on the adherend, the impact resistance from being deteriorated, and the shear adhesive strength and split adhesive strength from being weakened.

[0209] The content of the filler in the adhesive layer of the present embodiment can be appropriately adjusted when preparing the adhesive composition, which is a precursor of the adhesive layer.

[0210] When the silicone rubber particles or silicone composite particles are used as the filler, the content of the silicone rubber particles or silicone composite particles is preferably 15 to 35% by mass relative to 100% by mass of the adhesive layer.

[0211] When the acrylic-modified silicone particles are used as the filler, the content of the acrylic-modified silicone particles is preferably 1.0 to 20% by mass relative to 100% by mass of the adhesive layer.

[0212] In this embodiment, the volume ratio of the filler to the total volume of the adhesive layer is preferably 4 to 40%, more preferably 5 to 30%, even more preferably 5 to 20%, and most preferably 5 to 15%. When the volume ratio of the filler is 4% or more, the adhesive tape can be peeled off more easily and quickly. In addition, when the volume ratio of the filler is 40% or less, it is possible to prevent the adhesive layer from remaining on the adherend, the impact resistance from being deteriorated, and the shear adhesive strength and split adhesive strength from being weakened.

[0213] The volume ratio of the filler to the adhesive layer can be calculated from the following formulas (1) to (3). Adhesive Resin *1 Mass A (g) / Adhesive resin *1 Density A (g / cm 3 ) = Volume A of adhesive resin * 1 (cm 3 ) Formula (1) Mass of filler B (g) / Density of filler B (g / cm 3 ) = Filler volume B (cm 3 ) Formula (2) Filler volume B (cm 3 ) / (Adhesive resin *1 Volume A (cm 3 ) + filler volume B (cm 3 )) × 100 = Filler volume ratio (%) Formula (3) In the above formulas (1) and (3), *1 The adhesive resin represented by the formula (I) may contain other components described later. The density is a value measured in accordance with JIS Z 8804.

[0214] The pressure-sensitive adhesive tape of the present embodiment may be provided with one or more other layers as appropriate depending on the purpose. Examples of the other layers include a primer layer, an antistatic layer, a flame-retardant layer, a decorative layer, a conductive layer, a heat-conductive layer, and a release layer.

[0215] The adhesive tape of the present embodiment is not particularly limited in shape and size as long as it comprises a base layer and an adhesive layer on at least one surface of the base layer, and includes, for example, an adhesive tape having a shape and size suitable for attachment to a predetermined adherend (for example, an adhesive tape in a state after punching processing) and a sheet-like long adhesive tape (for example, an adhesive tape before being processed into a specific shape). In addition, the adhesive tape of the present embodiment can be arbitrarily provided with a non-adhesive gripping region, for example, for attachment to an adherend or peeling from an adherend.

[0216] The (average) thickness of the adhesive tape is not particularly limited and can be appropriately selected depending on the (average) thickness of the adhesive layer and the base layer, but is preferably 20 to 1000 μm, more preferably 30 to 600 μm, even more preferably 50 to 400 μm, and particularly preferably 100 to 250 μm.

[0217] In this specification, the "thickness of the adhesive tape" refers to the average thickness of a total of 25 points, measured by cutting the adhesive tape at 5 points at 100 mm intervals along the length and across the width, and measuring the thickness of the adhesive layer at 5 points at 100 mm intervals along the width on each cut surface using a TH-104 thickness meter for paper and film (manufactured by Tester Sangyo Co., Ltd.).

[0218] The hardness (type A hardness (Shore A hardness)) of the adhesive tape is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 15 to 90, more preferably 20 to 85, and even more preferably 50 to 85. When the Shore A hardness of the adhesive tape is within the above-mentioned preferred range, the adhesive tape can be easily peeled off. On the other hand, when the Shore A hardness is less than 10, the adhesive tape may tear when stretched to peel off, and when it exceeds 90, when the adhesive tape is stretched to be peeled off, the stress for stretching becomes too high and the adhesive tape may not be peelable.

[0219] The rubber hardness of the adhesive tape is Shore A hardness, and refers to a value measured in accordance with JIS K 6253 using a durometer (spring type rubber hardness tester) (model: GS-719G, manufactured by Teclock Corporation).

[0220] The stress of the adhesive tape at 25% elongation is preferably 0.15 to 82 MPa, more preferably 0.16 to 10 MPa, even more preferably 0.17 to 5 MPa, and most preferably 0.18 to 4.5 MPa. When the stress of the adhesive tape at 25% elongation is 0.15 MPa to 82 MPa, the adhesive tape can have a suitable adhesive strength, and can be relatively easily peeled off even when stretched and peeled off. On the other hand, when the stress of the adhesive tape at 25% elongation is less than 0.15 MPa, the adhesive tape may peel off when a load is applied in the shear direction of the adhesive tape while fixing hard adherends to each other. In addition, when the stress of the adhesive tape at 25% elongation exceeds 82 MPa, the force required to stretch the adhesive tape when peeling off the adhesive tape tends to be excessive.

[0221] The stress at 25% elongation of an adhesive tape refers to the stress value measured when the adhesive tape is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the length direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH, and elongated by 25%.

[0222] The breaking stress of the adhesive tape is not particularly limited and can be appropriately selected according to the purpose, but is preferably 10 to 100.0 MPa, more preferably 15 to 90.0 MPa, even more preferably 30 to 90.0 MPa, and particularly preferably 40 to 90.0 MPa. When the breaking stress of the adhesive tape is within the above-mentioned preferred range, the adhesive tape can be prevented from tearing even when the adhesive tape is quickly stretched and peeled off, and the load for stretching the adhesive tape does not become excessive, making it easy to perform the peeling operation. On the other hand, when the breaking stress of the adhesive tape is less than 10 MPa, the adhesive tape may tear when the adhesive tape is quickly stretched and peeled off, and when it exceeds 100.0 MPa, when the adhesive tape is stretched to be peeled off, it may not be stretched sufficiently and may not be peeled off. The force required to stretch and deform an adhesive tape also depends on the thickness of the adhesive tape. For example, when attempting to stretch a thick adhesive tape with a high breaking stress to make it removable, it may not be possible to stretch it sufficiently to make it removable.

[0223] The breaking stress of an adhesive tape refers to the stress value measured when the adhesive tape is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the lengthwise direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement conditions of 23°C and 50% RH, until the tape breaks.

[0224] The breaking elongation of the adhesive tape is not particularly limited and can be appropriately selected according to the purpose, but is preferably 400 to 2000%, more preferably 500 to 1800%, and even more preferably 600 to 1200%. When the breaking elongation of the adhesive tape is 400% or more, even if the adhesive tape is firmly attached to the adherend, when the adhesive tape is peeled off again, the stress for stretching the adhesive tape in the horizontal to vertical direction relative to the adherend surface is not too large, and the adhesive tape can be easily peeled off without excessive stretching when peeled off. In addition, when the breaking elongation is 2000% or less, when the adhesive tape is peeled off again, the stretching distance in the horizontal to vertical direction relative to the adherend surface is not too long, and work can be done in a small space. On the other hand, if the breaking elongation is less than 500%, when the adhesive tape is to be peeled off again, it may break when stretched horizontally to vertically relative to the application surface of the adherend, and may not be able to be peeled off. On the other hand, if the breaking elongation exceeds 1300%, when the adhesive tape is to be peeled off again, the stretching distance in the horizontal to vertical direction relative to the application surface of the adherend becomes too long, and workability may be reduced.

[0225] The breaking elongation of an adhesive tape refers to the tensile elongation measured when the adhesive tape is punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the length direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under measurement atmosphere conditions of 23°C and 50% RH, and broken.

[0226] The pressure-sensitive adhesive tape also has excellent impact resistance. Impact resistance can be confirmed, for example, by the method described in the "Evaluation of Impact Resistance" section of the Examples section below. In the evaluation of impact resistance, the height of the impact point at which peeling or destruction of the pressure-sensitive adhesive tape occurs can be appropriately selected within a range that does not impair the effects of the present invention, but is preferably 30 cm or more, more preferably 40 cm or more, even more preferably 50 cm or more, and particularly preferably 60 cm or more. If the height is less than 30 cm, there is a tendency that sufficient impact resistance cannot be obtained.

[0227] The storage modulus G' (23°C) of the adhesive tape is 1.0×10 4 ~1.0×10 8 Pa, preferably 5.0×10 4 ~5.0×10 7 Pa is more preferably 1.0×10 5 ~1.0×10 7 More preferably, the temperature is 3.0×10 Pa. 5 ~8.0×10 6 It is even more preferable that the stress at break of the adhesive tape is within the above range, so that the adhesive tape can easily follow the distortion of the adherend and can easily obtain excellent adhesive strength, and the dimensional stability of the adhesive tape can be ensured, so that suitable application workability can be obtained. As described above, the adhesive tape according to the present invention is also assumed to be a hard adherend such as metal or plastic, but has a large area. In general, the larger the adherend, the more difficult it is to mold the adhesive tape while suppressing distortion. If the adhesive tape has the above storage modulus range, the adhesive tape can follow the distortion of the adherend as described above, and suitable adhesive strength can be obtained.

[0228] The 180° peel adhesive strength of the pressure-sensitive adhesive tape is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 3 N / 20 mm to 50 N / 20 mm, more preferably 10 N / 20 mm to 50 N / 20 mm, and even more preferably 15 N / 20 mm to 45 N / 20 mm. When the 180° peel adhesive strength is within the above-mentioned preferred range, the pressure-sensitive adhesive tape has a moderate adhesive strength without causing peeling or slippage from the adherend, and can be easily peeled off when stretched horizontally to vertically relative to the application surface of the adherend for re-peelability.

[0229] In this specification, the 180° peel adhesive strength of the pressure-sensitive adhesive tape refers to a value measured in accordance with JIS Z 0237.

[0230] The pressure-sensitive adhesive tape of the present embodiment preferably has a shear adhesive strength of 1 MPa or more, preferably 0.7 to 4.0 MPa, more preferably 1.0 to 4.0 MPa, and even more preferably 1.5 to 4.0 MPa. When the shear adhesive strength is within the above-mentioned preferred range, it is possible to easily achieve both high load holding power and adhesiveness. The shear adhesive strength of the pressure-sensitive adhesive tape refers to a value measured by the method described in the examples below.

[0231] In the present embodiment, the method for producing the adhesive tape is not particularly limited and can be appropriately selected from known methods. The method for producing the adhesive tape of the present embodiment preferably includes an adhesive layer forming step, a base layer forming step, and a lamination step, and further includes other layer forming steps as necessary. The adhesive tape can also be produced by a multi-layer simultaneous formation step in which the adhesive layer forming step and the base layer forming step are performed simultaneously.

[0232] The adhesive layer forming step is not particularly limited as long as it can form an adhesive layer, and can be appropriately selected depending on the purpose, and examples thereof include a method of forming an adhesive layer on the surface of a release sheet by a heat press method, a casting method by extrusion molding, a uniaxial stretching method, a sequential secondary stretching method, a simultaneous biaxial stretching method, an inflation method, a tube method, a calendar method, a solution method, etc. Among these, the casting method by extrusion molding and the solution method are preferred.

[0233] The release sheet is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include paper such as kraft paper, glassine paper, and wood-free paper; resin films such as polyethylene, polypropylene (biaxially oriented polypropylene (OPP), uniaxially oriented polypropylene (CPP)), and polyethylene terephthalate (PET); laminated paper in which the above-mentioned paper and resin film are laminated together; and the above-mentioned paper that has been subjected to a sealing treatment with clay, polyvinyl alcohol, or the like and then subjected to a release treatment with silicone resin or the like on one or both sides. These may be used alone or in combination of two or more types.

[0234] The base layer forming step is not particularly limited as long as the base layer can be formed, and can be appropriately selected according to the purpose, and examples thereof include a heat press method, a casting method by extrusion molding, a uniaxial stretching method, a sequential secondary stretching method, a simultaneous biaxial stretching method, an inflation method, a tube method, a calendar method, and a solution method. These methods may be used alone or in combination of two or more. Among these, the casting method by extrusion molding, the inflation method, the tube method, the calendar method, and the solution method are preferred in terms of imparting suitable flexibility and extensibility to the base layer.

[0235] The base layer may be surface-treated in order to further improve the adhesion to the adhesive layer.

[0236] The surface treatment method is not particularly limited and can be appropriately selected from known methods as long as it does not impair the properties of the adhesive tape. Examples of the surface treatment method include sandblasting, surface polishing / rubbing, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet irradiation treatment, and oxidation treatment.

[0237] The lamination step is a step of laminating the base material layer and the adhesive layer. The method of laminating the base material layer and the adhesive layer is not particularly limited and can be appropriately selected from known methods, for example, a method of pressing and laminating the adhesive layer and the base material layer in a state of adhering to the release sheet formed in the adhesive layer forming step.

[0238] The adhesive tape according to the present invention can be suitably used for component fixing or temporary fixing in various industrial fields, such as fixing metal plates constituting relatively large electronic devices, such as flat-screen televisions, home appliances, and office automation equipment, fixing exterior parts to housings, and fixing rigid parts, such as exterior parts and batteries, to relatively small electronic devices, such as portable electronic terminals, cameras, and personal computers, as well as for applications such as labels displaying product information.

[0239] Although the embodiment of the present invention has been described above, the pressure-sensitive adhesive tape according to the present invention is not limited to the above example and can be modified as appropriate. EXAMPLES

[0240] The present invention will be described in detail below using examples, but the scope of the present invention is not limited to the following examples. Measurements and evaluations of the base layer, adhesive layer, and adhesive tape obtained in each example and comparative example were performed based on the following methods.

[0241] (1) Measurement of the breaking stress and breaking elongation of the base layer Each base material layer was punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and the breaking stress and breaking elongation of the base material layer were measured by pulling them in the length direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measurement atmosphere of 23°C and 50% RH. The results are shown in Table 1 below.

[0242] (2) Measurement of 50% modulus of base layer Each base material layer was punched out into a dumbbell shape with a gauge length of 20 mm and a width of 5 mm, and pulled in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under conditions of a measurement atmosphere of 23°C and 50% RH, to measure the stress value when the base material layer was stretched by 50%.

[0243] (3) Measurement of the thickness of the base layer and the adhesive layer The base layer and adhesive layer were cut lengthwise at 5 locations at 100 mm intervals and widthwise at 5 locations, and the thickness of each cut surface was measured at 5 locations at 100 mm intervals in the widthwise direction using a TH-104 thickness measuring instrument for paper and film (manufactured by Tester Sangyo Co., Ltd.). The average value of the total 25 thicknesses was used as the thickness of the base layer and adhesive layer.

[0244] (4) Measurement of the average particle size of the filler The average particle size (primary particle size) of the filler was measured by using a measuring device (Microtrac) that uses a laser diffraction scattering method.

[0245] (5) Evaluation of 180° peel adhesion The 180° peel adhesive strength was measured in accordance with JIS Z 0237. Specifically, each adhesive tape was cut to a length of 150 mm and a width of 20 mm, and one side of the adhesive tape was backed with a PET film having a thickness of 25 μm. Next, the other side of the adhesive tape was attached to a stainless steel plate (length 100 mm, width 30 mm, thickness 3 mm) under conditions of an atmosphere of 23° C. and 50% RH, and the laminated structure of the adhesive tape and the stainless steel plate was pressed and bonded by one reciprocating motion with a roller while applying a load of 2 kg to the laminated structure, and then the laminated structure was left to stand for 1 hour under conditions of an atmosphere of 23° C. and 50% RH to prepare a test piece. The adhesive tape of the test piece was then stretched in the 180° direction (horizontal direction) at a tensile speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under conditions of an atmosphere of 23°C and 50% RH, and the 180° peel adhesive strength of the adhesive tape was measured.

[0246] (6) Evaluation of shear adhesive strength The prepared adhesive tape was cut into a size of 25 mm wide x 25 mm long, and attached to the surface of a clean, smooth-surfaced stainless steel plate 1 (treated with hairline polishing using No. 360 waterproof abrasive paper) in an atmosphere of 23°C and 50% RH so that the adhesive area was 25 mm x 25 mm, and the opposite side was attached to the surface of a clean, smooth-surfaced stainless steel plate 2 (treated with hairline polishing using No. 360 waterproof abrasive paper) in an atmosphere of 23°C so that the adhesive area was 25 mm x 25 mm, and then they were pressed together by rolling them back and forth once with a 5 kg roller, and left in an environment of 23°C for 24 hours to prepare a test piece. Then, with the stainless steel plate 1 constituting the test piece fixed, the stainless steel plate 2 was pulled in the shear direction of the adhesive tape at a speed of 300 mm / min using a Tensilon tensile tester in an atmosphere of 23°C and 50% RH to measure the shear adhesive strength.

[0247] (7) Evaluation of high load retention One side of each adhesive tape cut to 25 mm wide x 25 mm long was pressed and bonded to a SUS304 steel plate of 25 mm wide x 80 mm wide specified in JIS Z0237 by a roller weighing 5 kg at room temperature at a speed of 300 mm per minute, and then left at 23 ° C for 30 minutes. Then, the other side of the test piece was pressed and bonded to a SUS304 steel plate of 25 mm wide x 80 mm wide specified in JIS Z0237 by a roller weighing 5 kg at room temperature at a speed of 300 mm per minute. Then, left in a 40 ° C atmosphere for 30 minutes. After this, a 5 kg weight was attached to the gripping portion of the test piece, and the test was started by hanging it down, and the time until it fell under 23 ° C 50% RH was measured. For high load retention, a drop time of 120 minutes or more was considered to be passed. Also, a drop time of less than 120 minutes was considered to be failed.

[0248] (8) Evaluation of removability The removability evaluation was carried out by stretching the grip part provided at one end of the adhesive tape in the longitudinal direction (180° direction) and by stretching the adhesive tape in the 90° direction to the longitudinal direction (90° direction). The details are explained below. (8-1) Removability Evaluation 1 (180° direction) (Initial removability in removability evaluation 1 (180° direction)) When the adhesive tape, measuring 10 mm wide and 60 mm long, was applied to a clean, smooth aluminum plate, the adhesive tape was applied in a state where the gripping part protruded from the aluminum plate in order to make a 10 mm wide x 10 mm long portion of the adhesive tape into a gripping part. The other side of the adhesive tape was then applied to a clean, smooth acrylic plate, and a roller was applied back and forth once while applying a load of 2 kg to obtain a test piece. After application, the tape was left in an atmosphere of 23°C and 50% RH for 60 minutes, and then 2 At 3°C ​​and 50% RH, the gripped portion of the adhesive tape was stretched by hand in the longitudinal direction of the adhesive tape at a speed of approximately 300 mm / min. Out of the 10 tests, the degree of breakage of the adhesive tape and the degree of adhesive remaining on the adherend after the adhesive tape was peeled off were visually evaluated according to the following criteria. : The adhesive tape was peeled off cleanly all 10 times without breaking or leaving any adhesive residue. ◯: The adhesive tape was peeled off without breaking all 10 times, but adhesive residue was left behind in at least one case. △: The adhesive tape was peeled off cleanly 6 to 9 times without breaking or leaving any adhesive residue. ×: The adhesive tape broke or adhesive residue was left 5 to 10 times, or the adhesive tape could not be stretched and peeled off.

[0249] (Removability evaluation 1 (180° direction)) When the adhesive tape, 10 mm wide x 60 mm long, was applied to a clean, smooth aluminum plate, the adhesive tape was applied in a state where the gripping part protruded from the aluminum plate in order to make a 10 mm wide x 10 mm long portion of the adhesive tape into a gripping part. The other side of the adhesive tape was then applied to a clean, smooth acrylic plate, and a roller was applied back and forth once while applying a load of 2 kg to obtain a test piece. After application, the tape was left in an atmosphere of 23°C and 50% RH for 3 days, and then 2 At 3°C ​​and 50% RH, the gripped portion of the adhesive tape was stretched by hand in the longitudinal direction of the adhesive tape at a speed of approximately 300 mm / min. Out of the 10 tests, the degree of breakage of the adhesive tape and the degree of adhesive remaining on the adherend after the adhesive tape was peeled off were visually evaluated according to the following criteria. : The adhesive tape was peeled off cleanly all 10 times without breaking or leaving any adhesive residue. ◯: The adhesive tape was peeled off without breaking all 10 times, but adhesive residue was left behind in at least one case. △: The adhesive tape was peeled off cleanly 6 to 9 times without breaking or leaving any adhesive residue. ×: The adhesive tape broke or adhesive residue was left 5 to 10 times, or the adhesive tape could not be stretched and peeled off.

[0250] (8-2)Removability 2 (90° direction) (Initial removability at removability 2 (90° direction)) When the adhesive tape, measuring 10 mm wide and 60 mm long, was applied to a clean, smooth aluminum plate, the adhesive tape was applied in a state where the gripping part protruded from the aluminum plate in order to make a 10 mm wide x 10 mm long portion of the adhesive tape into a gripping part. The other side of the adhesive tape was then applied to a clean, smooth acrylic plate, and a roller was applied back and forth once while applying a load of 2 kg to obtain a test piece. After application, the tape was left in an atmosphere of 23°C and 50% RH for 60 minutes, and then 2 At 3°C ​​and 50% RH, the gripping portion was stretched by hand at a speed of approximately 300 mm / min in a direction at 90° to the longitudinal direction of the adhesive tape. Out of the 10 tests, the degree of breakage of the adhesive tape and the degree of adhesive remaining on the adherend after the adhesive tape was peeled off were visually evaluated according to the following criteria. : The adhesive tape was peeled off cleanly all 10 times without breaking or leaving any adhesive residue. ◯: The adhesive tape was peeled off without breaking all 10 times, but adhesive residue was left behind in at least one case. △: The adhesive tape was peeled off cleanly 6 to 9 times without breaking or leaving any adhesive residue. ×: The adhesive tape broke or adhesive residue was left 5 to 10 times, or the adhesive tape could not be stretched and peeled off.

[0251] (Removability over time at 90° angle) When the adhesive tape, 10 mm wide x 60 mm long, was applied to a clean, smooth aluminum plate, the adhesive tape was applied in a state where the gripping part protruded from the aluminum plate in order to make a 10 mm wide x 10 mm long portion of the adhesive tape into a gripping part. The other side of the adhesive tape was then applied to a clean, smooth acrylic plate, and a roller was applied back and forth once while applying a load of 2 kg to obtain a test piece. After application, the tape was left in an atmosphere of 23°C and 50% RH for 3 days, and then 2 At 3°C ​​and 50% RH, the gripping portion was stretched by hand at a speed of approximately 300 mm / min in a direction at 90° to the longitudinal direction of the adhesive tape. Out of the 10 tests, the degree of breakage of the adhesive tape and the degree of adhesive remaining on the adherend after the adhesive tape was peeled off were visually evaluated according to the following criteria. : The adhesive tape was peeled off cleanly all 10 times without breaking or leaving any adhesive residue. ◯: The adhesive tape was peeled off without breaking all 10 times, but adhesive residue was left behind in at least one case. △: The adhesive tape was peeled off cleanly 6 to 9 times without breaking or leaving any adhesive residue. ×: The adhesive tape broke or adhesive remained after 5 to 10 times. Or the adhesive tape could not be stretched and peeled off.

[0252] (9) Evaluation of storage stability of adhesive strength The 180° peel adhesive strength of the prepared adhesive tape was measured before and after it was left at 40°C for two weeks. The measurement method used was the same as that described in the above-mentioned section "(5) Evaluation of 180° peel adhesive strength". The 180° peel adhesive strength of the adhesive tape before it was left at 40°C for two weeks was defined as the initial adhesive strength (P0), and the 180° peel adhesive strength after it was left as the adhesive strength after two weeks at 40°C (P2). The storage stability of the adhesive tape was calculated as (P2 / P0) x 100. A value of 80% or more was considered to be acceptable.

[0253] Next, the materials used in the examples and comparative examples are as follows. <Base material (1)> A styrene-ethylenebutylene-styrene copolymer and a styrene-ethylenebutylene copolymer resin composition (1) were used as the substrate material for the substrate (1). The resin composition (1) contained 29% by mass of the styrene-derived structural unit represented by the above chemical formula (A), and the ratio of the styrene-ethylenebutylene copolymer to the total amount of the resin composition was 0.5% by mass. The resin composition (1) was used to prepare a substrate (1) having a thickness of 50 μm by heat pressing (pressure 0.5 MPa, press plate temperature 130° C., press time 2 minutes). The breaking stress of the substrate (1) was 80 MPa. The breaking elongation was 700%. The stress (modulus) at 50% elongation was 3 MPa.

[0254] <Base material (2)> A resin composition (2) of styrene-isoprene copolymer and styrene-isoprene-styrene copolymer was used as the substrate material for the substrate (2). The resin composition (2) contained 25% by mass of the styrene-derived structural unit represented by the above chemical formula (A), and the ratio of the styrene-isoprene copolymer to the total amount of the resin composition (2) was 16% by mass. The resin composition (2) was heat pressed (pressure 0.5 MPa, press plate temperature 130°C, press time 2 minutes) to prepare a substrate (2) with a thickness of 50 μm. The breaking stress of the substrate (2) was 10 MPa. The breaking elongation was 1200%. The stress (modulus) at 50% elongation was 1 MPa.

[0255] <Base material (3)> The substrate (3) used was a polyester film manufactured by Toray called "Lumirror S10 50 μm." The breaking stress of the substrate (3) was 220 MPa. The breaking elongation was 180%. The stress (modulus) at 50% elongation was 130 MPa. <Adhesive composition> The pressure-sensitive adhesive composition of the present invention contains the following filler and pressure-sensitive adhesive resin. <<Filler>> Silicone particles (1) Silicone (1) is a particle having a silicone resin surface and a silicone rubber interior (Shin-Etsu Chemical Co., Ltd., KMP-602, volume average particle size: 30 μm, particle size distribution (D 90 / D 10 ):5.2) was used. Silicone particles (2) Silicone particles (2) are particles whose surface is silicone resin and whose interior is silicone rubber (Shin-Etsu Chemical Co., Ltd., KMP-601, volume average particle size: 12 μm, particle size distribution (D 90 / D 10 ):4.4) was used.

[0256] <<Adhesive resin>> <<Synthesis of triblock copolymer>> (Synthesis Example 1) In a flask with an internal volume of 1000 ml, the inside of which had been replaced with argon, 500 ml of dry toluene and 80 ml of a solution of 0.75 g of bis(pentamethylcyclopentadienyl)samarium tetrahydrofuranate complex [(C5Me5)2SmMe(THF)] as a polymerization initiator were added to prepare a mixed solution. 12.0 ml of methyl methacrylate (MMA) was added to the mixed solution at 0°C and stirred at 0°C for 30 minutes. Then, 20 ml of the solution was sampled from the system (Sample 1). After the polymerization of MMA, the polymerization reaction system was cooled to -78°C, and 88.0 ml of n-butyl acrylate (nBA) was added as the second monomer and stirred at -78°C for 3 hours. Then, 20 ml of the solution was sampled from the system (Sample 2). After the polymerization of nBA, 12.0 ml of MMA was added to the polymerization system as the third monomer at -78°C and the solution was stirred. After the solution became homogeneous, it was heated to 0°C and stirred for another hour. The polymerization was terminated by adding 50 ml of methanol to the resulting reaction mixture and reacting at room temperature for 2 hours. The reaction solution after the polymerization was terminated was poured into a large amount of hexane to obtain a white precipitate. A part of the white precipitate was then sampled (sample 3).

[0257] NMR measurement, DSC measurement, and GPC (gel permeation chromatography) measurement were performed on each polymer in the above samples 1 to 3. Then, based on the measurement results, the number average molecular weight (Mn), PMMA / PnBA (polymethyl methacrylate block / polyn-butyl acrylate block) ratio, etc. were obtained, and it was confirmed that the above white precipitate was a triblock copolymer (PMMA-b-PnBA-b-PMMA) of polymethyl methacrylate (PMMA) block-polyn-butyl acrylate (PnBA) block-polymethyl methacrylate (PMMA) block. It was also confirmed that the PMMA block portion of the triblock copolymer (PMMA-b-PnBA-b-PMMA, hereinafter referred to as triblock copolymer (1)) had a syndiotacticity of 71%, a glass transition temperature of 113.7°C, a glass transition temperature of -46.8°C, an Mn of the entire copolymer of 95,936, an Mw / Mn (molecular weight distribution) of the entire copolymer of 1.09, and a ratio of the polymer blocks of PMMA (11% by mass)-PnBA (78% by mass)-PMMA (11% by mass).

[0258] (Synthesis Example 2) In a flask with a capacity of 1000 ml and purged with argon, 500 ml of dry toluene and 80 ml of a solution of 0.75 g of bis(pentamethylcyclopentadienyl)samarium tetrahydrofuranate complex [(C5Me5)2SmMe(THF)] as a polymerization initiator were added to prepare a mixed solution. 6.0 ml of methyl methacrylate (MMA) was added to the mixed solution at 0°C and stirred at 0°C for 30 minutes. Then, 20 ml of the solution was sampled from the system (Sample 4). After the polymerization of MMA, the polymerization reaction system was cooled to -78°C, and 27.2 ml of n-butyl acrylate (nBA) and 22.1 ml of 2-ethylhexyl acrylate (2EHA) were added as the second monomer and stirred at -78°C for 3 hours. 20 ml of the solution was sampled from the system (Sample 5). After the polymerization of nBA, 6.0 ml of MMA was added to the polymerization system as the third monomer at -78°C, and the solution was stirred. After the solution became homogeneous, it was heated to 0°C and stirred for another hour. The polymerization was terminated by adding 50 ml of methanol to the resulting reaction mixture and reacting at room temperature for 2 hours. The reaction solution after the polymerization termination was poured into a large amount of hexane, and a white precipitate was obtained. Then, a part of the white precipitate was sampled (sample 6). NMR measurement, DSC measurement, and GPC (gel permeation chromatography) measurement were performed on each polymer in the above samples 4 to 6. Then, based on the measurement results, the number average molecular weight (Mn), PMMA / PnBA / P2EHA (polymethyl methacrylate / polyn-butyl acrylate / poly-2-ethylhexyl acrylate) ratio, etc. were obtained, and it was confirmed that the above white precipitate was a triblock copolymer (PMMA-b-PnBA / 2EHA-b-PMMA) of polymethyl methacrylate (PMMA) block-polyn-butyl acrylate (PnBA) / poly-2-ethylhexyl acrylate (2EHA) block-polymethyl methacrylate (PMMA) block. The PMMA block of the triblock copolymer (PMMA-b-PnBA / 2EHA-b-PMMA, hereinafter referred to as triblock copolymer (2)) had a syndiotacticity of 75%, a glass transition temperature of 105.8°C, a glass transition temperature of -53.6°C, an Mn of the entire copolymer of 51370, an Mw / Mn (molecular weight distribution) of 1.15, and a ratio of each polymer block of PMMA (10% by mass). )-PnBA (44% by mass) / 2EHA (36% by mass)-PMMA (10% by mass).

[0259] (Synthesis Example 3) In a flask with a capacity of 1000 ml and the inside of which had been replaced with argon, 500 ml of dry toluene and 80 ml of a dry toluene solution containing 0.75 g of bis(pentamethylcyclopentadienyl)samarium tetrahydrofuranate complex [(C5Me5)2SmMe(THF)] as a polymerization initiator were added to prepare a mixed solution. 20.0 ml of methyl methacrylate (MMA) was added to the mixed solution at 0°C and stirred at 0°C for 30 minutes. 20 ml of the solution was sampled from the system (Sample 7). After the polymerization of MMA, the polymerization reaction system was cooled to -78°C, and 148.5 ml of n-butyl acrylate (nBA) was added as the second monomer and stirred at -78°C for 3 hours. 20 ml of the solution was sampled from the system (Sample 8). After the polymerization of nBA, 20.0 ml of MMA was added to the polymerization system as the third monomer at -78°C and the solution was stirred. After the solution became homogeneous, it was heated to 0°C and stirred for another hour. The polymerization was terminated by adding 50 ml of methanol to the resulting reaction mixture and reacting at room temperature for 2 hours. The reaction solution after the polymerization was terminated was poured into a large amount of hexane to obtain a white precipitate. A part of the white precipitate was then sampled (sample 9). NMR measurement, DSC measurement, and GPC (gel permeation chromatography) measurement were performed on each of the polymers in Samples 7 to 9. Then, based on the measurement results, the number average molecular weight (Mn), PMMA / PnBA (polymethyl methacrylate block / polyn-butyl acrylate block) ratio, etc. were obtained, and it was confirmed that the white precipitate was a triblock copolymer (PMMA-b-PnBA-b-PMMA) having polymethyl methacrylate (PMMA) block-polyn-butyl acrylate (PnBA) block-polymethyl methacrylate (PMMA) block. It was confirmed that the PMMA block portion of the triblock copolymer (PMMA-b-PnBA-b-PMMA, hereinafter referred to as triblock copolymer (3)) had a syndiotacticity of 71%, a glass transition temperature of 108.2°C, a glass transition temperature of -47.2°C, an Mn of the entire copolymer of 159,585, an Mw / Mn (molecular weight distribution) of 1.05, and a ratio of the polymer blocks of PMMA (11% by mass)-PnBA (78% by mass)-PMMA (11% by mass).

[0260] <<Other adhesive resins>> (Synthesis Example 4) The adhesive resin used was an acrylic random copolymer obtained by the following synthesis. 97.97 parts by mass of n-butyl acrylate, 2 parts by mass of acrylic acid, and 0.03 parts by mass of 4-hydroxybutyl acrylate were fed to ethyl acetate containing 0.2 parts by mass of azobisisobutyronitrile as a polymerization initiator, and solution polymerized at 77°C for 8 hours to obtain an acrylic random copolymer. Mw was 700,000, and Mw / Mn (molecular weight distribution) was 4.7. (SIS rubber) The adhesive resin used was SIS rubber (styrene triblock copolymer) (Zeon Corporation Quintac 3270, styrene content 24%, SI diblock content 67%). The triblock copolymer had an Mw of 175,000 and an Mw / Mn (molecular weight distribution) of 1.05. The diblock copolymer had an Mw of 84,000 and an Mw / Mn (molecular weight distribution) of 1.05.

[0261] <Preparation of Pressure-Sensitive Adhesive Resin Composition> Adhesive composition (1) 100 parts by mass of the triblock copolymer (1) obtained in the above-mentioned Synthesis Example 1 was mixed and stirred with 50 parts by mass of a rosin ester tackifier resin (Super Ester A100, Arakawa Chemical Industries, Ltd., softening point 100°C), and then ethyl acetate was added to obtain an adhesive resin solution (1) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (1), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (1) with a solid content of 40% by mass.

[0262] Adhesive composition (2) 100 parts by mass of the triblock copolymer (1) obtained in the above-mentioned Synthesis Example 1 was mixed and stirred with 50 parts by mass of a rosin ester tackifier resin (Haritac PCJ, Harima Chemicals Co., Ltd., softening point 135°C), and then ethyl acetate was added to obtain an adhesive resin solution (1) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (2) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (1), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (2) with a solid content of 40% by mass.

[0263] Adhesive composition (3) 100 parts by mass of the triblock copolymer (1) obtained in the above-mentioned Synthesis Example 1 was mixed and stirred with 50 parts by mass of a terpene phenol-based tackifier resin (YS Polystar T160, Yasuhara Chemical Co., Ltd., softening point 160°C), and then ethyl acetate was added to obtain an adhesive resin solution (3) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (2) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (3), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (3) with a solid content of 40% by mass.

[0264] Adhesive composition (4) 100 parts by mass of the triblock copolymer (1) obtained in the above-mentioned Synthesis Example 1 was mixed and stirred with 50 parts by mass of a terpene phenol-based tackifier resin (YS Polystar T130, Yasuhara Chemical Co., Ltd., softening point 130°C), and then ethyl acetate was added to obtain an adhesive resin solution (4) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (2) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (4), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (4) with a solid content of 40% by mass.

[0265] Adhesive composition (5) 100 parts by mass of the triblock copolymer (1) obtained in the above-mentioned Synthesis Example 1 was mixed and stirred with 10 parts by mass of a terpene phenol-based tackifier resin (YS Polystar T130, Yasuhara Chemical Co., Ltd., softening point 130°C), and then ethyl acetate was added to obtain an adhesive resin solution (4) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (2) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (4), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (5) with a solid content of 40% by mass.

[0266] Adhesive composition (6) 100 parts by mass of the triblock copolymer (1) obtained in the above-mentioned Synthesis Example 1 was mixed and stirred with 75 parts by mass of a terpene phenol-based tackifier resin (YS Polystar T130, Yasuhara Chemical Co., Ltd., softening point 130°C), and then ethyl acetate was added to obtain an adhesive resin solution (4) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (2) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (4), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (6) with a solid content of 40% by mass.

[0267] Adhesive composition (7) 100 parts by mass of the triblock copolymer (2) obtained in the above-mentioned Synthesis Example 2 was mixed and stirred with 50 parts by mass of a terpene phenol-based tackifier resin (YS Polystar T130, Yasuhara Chemical Co., Ltd., softening point 130°C), and then ethyl acetate was added to obtain an adhesive resin solution (5) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (5), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (7) with a solid content of 40% by mass.

[0268] Adhesive composition (8) 100 parts by mass of the triblock copolymer (3) obtained in the above-mentioned Synthesis Example 3 was mixed and stirred with 50 parts by mass of a terpene phenol-based tackifier resin (YS Polystar T160, Yasuhara Chemical Co., Ltd., softening point 160°C), and then ethyl acetate was added to obtain an adhesive resin solution (3) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the adhesive resin solution (3), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (8) with a solid content of 40% by mass.

[0269] Adhesive composition (9) 100 parts by mass of the triblock copolymer (1) obtained in the above-mentioned Synthesis Example 1 was mixed and stirred with 50 parts by mass of a terpene phenol-based tackifier resin (YS Polystar T130, Yasuhara Chemical Co., Ltd., softening point 130°C), and then ethyl acetate was added to obtain a pressure-sensitive adhesive composition (9) having a solid content of 40% by mass.

[0270] Adhesive composition (10) As the adhesive resin, 100 parts by mass of a styrene triblock copolymer (Zeon Corporation Quintac 3270, styrene content 24%, SI diblock content 67%) was mixed and stirred with 50 parts by mass of a rosin tackifier resin (Super Ester A-100, Arakawa Chemical Co., Ltd., softening point 100°C), and then toluene was added to obtain an adhesive resin solution (6) with a solid content of 35% by mass. 38 parts by mass of silicone particles (1) and toluene were added to 100 parts by mass of the solid content of the adhesive resin solution (6), and the mixture was stirred and mixed uniformly to obtain an adhesive composition (10) with a solid content of 40% by mass.

[0271] Adhesive composition (11) 100 parts by mass of the acrylic random copolymer obtained in the above-mentioned Synthesis Example 4 was mixed and stirred with 5 parts by mass of a rosin-based tackifier resin (Haritac PCJ, Harima Chemicals Co., Ltd., softening point 135°C) and 45 parts by mass of a petroleum-based tackifier resin (FTR6125, Mitsui Chemicals Co., Ltd., softening point 125°C), and then ethyl acetate was added to obtain a pressure-sensitive adhesive resin solution (7) with a solid content of 35% by mass. Next, 38 parts by mass of silicone particles (1) and ethyl acetate were added to 100 parts by mass of the solid content of the pressure-sensitive adhesive resin solution (7), and the mixture was stirred and mixed uniformly to obtain a pressure-sensitive adhesive composition (11) with a solid content of 40% by mass.

[0272] 3. "Adhesive tape manufacturing" Example 1 The adhesive composition (1) was applied to a release liner (Film Vina 75E-0010GT, manufactured by Fujimori Kogyo Co., Ltd., hereinafter the same) with an applicator so that the thickness after drying was 50 μm, and dried at 80 ° C for 3 minutes to prepare an adhesive layer. Next, both sides of the substrate (1) as a base layer were corona-treated so that the wet tension was 52 mN / m, and then the adhesive layer was attached to both sides, and the laminated structure of the substrate layer and the adhesive layer was pressed at 0.2 MPa and laminated to produce the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above method, and the results are shown in Table 1.

[0273] Example 2 An adhesive tape of Example 2 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (2) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0274] Example 3 An adhesive tape of Example 3 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (3) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0275] Example 4 An adhesive tape of Example 4 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (4) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0276] Example 5 An adhesive tape of Example 5 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (5) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0277] Example 6 An adhesive tape of Example 6 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (6) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0278] Example 7 An adhesive tape of Example 7 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (7) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0279] Example 8 An adhesive tape of Example 8 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (8) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0280] Example 9 An adhesive tape of Example 9 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (9) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1.

[0281] Example 10 An adhesive tape of Example 10 was produced in the same manner as in Example 4, except that in the production of the adhesive tape of Example 1, the substrate (1) was changed to the substrate (2). The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 1. Comparative Example 1 An adhesive tape of Comparative Example 1 was produced in the same manner as in Example 1, except that the adhesive composition (1) was changed to the adhesive composition (10) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 2.

[0282] Comparative Example 2 An adhesive tape of Comparative Example 2 was produced in the same manner as in Example 1, except that in the production of the adhesive tape of Example 1, adhesive composition (1) was changed to adhesive composition (11). The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 2. Note that the product of the softening point temperature [°C] of the tackifier resin and the amount of the tackifier resin added (the amount of the tackifier resin added when the triblock copolymer is taken as 100 parts by mass) in Comparative Example 2 was 6300 (=135°C x 5 parts by mass + 125°C x 45 parts by mass).

[0283] Comparative Example 3 An adhesive tape of Comparative Example 3 was produced in the same manner as in Example 1, except that the substrate (1) was changed to the substrate (3) in the production of the adhesive tape of Example 1. The obtained adhesive tape was evaluated by the above-mentioned method, and the results are shown in Table 2.

[0284] [Table 1]

[0285] [Table 2]

[0286] From the experimental results in Tables 1 and 2 above, it was confirmed that the pressure-sensitive adhesive tape of the present invention has excellent adhesive strength in terms of high load holding power, removability over time, and storage stability compared to the comparative examples.

Claims

1. An adhesive tape having a base layer and an adhesive layer, The base layer has a breaking stress of 1 to 100 MPa and a breaking elongation of 300 to 3000%, The adhesive layer comprises a tackifier resin and a compound represented by the general formula (1): 【Chemistry 1】 (In the above general formula (1), A, B, and C each independently represent a repeating unit, A and C each independently represent a methacrylic acid alkyl ester monomer unit; B represents an alkyl acrylate monomer unit; p, q and r each independently represent the degree of polymerization of each monomer unit; A and C may be the same or different methacrylic acid alkyl ester monomer units having different chemical structures. In the above general formula (1), * is a bond representing a bond to another atom. The adhesive layer contains the triblock copolymer in an amount of 30 to 100% by mass based on the total adhesive resin, the ratio of rr triads in the syndiotacticity of the polymer blocks of the [-(A)p-] and [-(C)r-] parts of the triblock copolymer is 65% or more; The pressure-sensitive adhesive tape has a softening point temperature [°C] of the tackifier resin x the amount of the tackifier resin added (the amount of the tackifier resin added when the triblock copolymer is taken as 100 parts by mass) of 6,500 to 13,000.

2. 2. The pressure-sensitive adhesive tape according to claim 1, wherein the triblock copolymer has a weight average molecular weight Mw of 50,000 to 300,000 and a number average molecular weight Mn of 50,000 to 300,000.

3. The pressure-sensitive adhesive tape according to claim 1 or 2, wherein the tackifier resin has a softening point of 95° C. or higher.

4. The pressure-sensitive adhesive tape according to any one of claims 1 to 3, wherein the base layer contains a vinyl aromatic block copolymer.

5. The pressure-sensitive adhesive tape according to claim 4, wherein the vinyl aromatic block copolymer contained in the base layer is at least one selected from the group consisting of a styrene-isoprene-butadiene-styrene block copolymer, a styrene-butadiene-styrene block copolymer, a styrene-ethylene-butylene block copolymer, a styrene-ethylene-propylene block copolymer, and hydrogenated types thereof.

6. The pressure-sensitive adhesive tape according to any one of claims 1 to 5, which has a peel adhesive strength of 5 N / 20 mm or more.

7. The pressure-sensitive adhesive tape according to any one of claims 1 to 6, which has a shear adhesive strength of 1.0 MPa or more.

8. The adhesive tape according to any one of claims 1 to 7, wherein the adhesive layer contains 10 to 150 parts by mass of the tackifier resin per 100 parts by mass of the triblock copolymer.

9. The adhesive tape according to any one of claims 1 to 8, wherein the adhesive layer contains a filler.

Citation Information

Patent Citations

  • Surface protection pressure-sensitive adhesive sheet

    JP2013136653A

  • Adhesive composition

    JP2014148570A

  • Adhesive tape and tape substrate used therefor

    JP2015124289A

  • Stretch releasable adhesive article

    JP2016026255A

  • Adhesive composition and adhesive tape

    JP2016183275A